S-linked quinone polymers, vulcanized carbon substrates, and related composites, compositions, electrode materials, electrodes, electrochemical cells, batteries, methods, and systems
S-linked quinone polymers and sulfurized carbon matrices enhance battery performance by providing high-capacity, long-life, and safe cathode materials for electrochemical cells, addressing the limitations of existing technologies.
Patent Information
- Application Number
- CN202380039285.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-09
- Filing Date
- 2023-05-08
- Publication Date
- 2024-12-27
AI Technical Summary
Existing battery technologies face challenges in producing high-capacity, long-life, safe, and cost-effective energy storage devices, particularly for large-scale applications such as electric vehicles and utility grid storage.
The development of S-linked quinone polymers and sulfurized carbon matrices, which are used to create high-performance cathode materials for electrochemical cells and batteries, offering high capacity, energy density, safety, and good cycling stability with non-aqueous electrolytes.
These materials enable batteries with high capacity, long life, low safety hazards, and cost-effectiveness, suitable for applications like electric vehicles and grid storage.
Smart Images

Figure CN119213056A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to U.S. Provisional Application No. 63 / 339,684, filed on May 9, 2022, with Docket No. P2678-USP, entitled “S-linked Quinone Polymers, Sulfurized Carbon Matrices and Related Composites, Compositions, Electrode Material, Electrodes, Electrochemical Cells, Batteries, Methods and Systems,” the contents of which are incorporated herein by reference. This application may also be related to U.S. Application No. 16 / 593,935, filed on October 4, 2019, entitled “Crosslinked Polymers and Related Compositions, Electrochemical Cells, Batteries, Methods and Systems”, U.S. Provisional Application No. 62 / 741,519, filed on October 4, 2018, entitled “Quinone-comprising network polymers as stable, high capacity organic electrode materials” with Docket No. ALNX_0001, U.S. Provisional Application No. 63 / 116,123, filed on November 19, 2020, entitled “Organic Electrode Materials for Zinc Batteries and Their Applications” with Docket No. P2551-USP, and U.S. Provisional Application No. 63 / 116,123, filed on June 28, 2021, entitled “Organic Electrode Materials for Zinc Batteries and Their Applications” with Docket No. P2551-USP2. Their Applications", the contents of each of which are incorporated herein by reference in their entirety. Technical Field
[0003] The present disclosure relates to electrode active materials and battery systems, characterized in that the electrodes comprise an organosulfur redox active polymer and a matrix. In particular, the present disclosure relates to S-linked quinone polymers, sulfurized carbon matrices and related composite materials, compositions, electrode materials, electrodes, electrochemical cells, batteries, methods and systems that can be used to improve electrochemical cells and battery performance. Background Art
[0004] Performance, economics, and safety have been at the center of various efforts to improve electrode active materials and battery technologies.
[0005] However, despite recent advances, the production of highly reliable, high-capacity, long-life, inexpensive and / or safe energy storage devices remains challenging, especially with respect to batteries for large-scale applications, such as in electric vehicles, utility grid storage to support renewable power generation, or whole-home backup battery installations. Summary of the invention
[0006] Described herein are S-linked quinone polymers, sulfurized carbon matrices and related composites, compositions, electrode materials, electrodes, electrochemical cells, batteries, methods and systems that, in several embodiments, allow for the production of high performance redox active materials that can be used as cathode active materials in electrochemical cells and batteries with high capacity, high energy density, safety, good cycling stability and long life with non-aqueous electrolytes.
[0007] According to a first aspect, an S-linked quinone polymer is described, wherein the S-linked quinone polymer is an S-linked quinone homopolymer represented by formula (I)
[0008] -[MS p ]- m
[0009] (I)
[0010] in
[0011] M is a redox active monomeric quinone moiety having a redox potential of 0.5 V to 3.5 V relative to the Li / Li+ electrode potential under standard conditions, wherein the standard conditions for measuring all potentials are at 298 K, 1 atm, and 1 M solution.
[0012] p refers to the number of sulfur atoms attached to the redox-active monomeric quinone moiety M, and p ranges from 1 to 5.
[0013] When p is 1, S p is a sulfide, or when p is 2 to 5, S p For polysulfide,
[0014] m ranges from 5 to 10,000,
[0015] wherein the S-linked quinone polymer has a weight average molecular weight of at least 1,000 Daltons and a solubility in tetrahydrofuran (THF) at 21° C. at 1 atmosphere of equal to or less than 1.0 microgram / mL.
[0016] According to a second aspect, an S-linked quinone polymer is described, wherein the S-linked quinone copolymer is represented by formula (II)
[0017] -[M1-S p1 ] m1 -co-[M2-S p2 ]- m2
[0018] (II)
[0019] in
[0020] M1 and M2 are each a redox-active monomeric quinone moiety comprising a redox potential of 0.5 V to 3.5 V relative to the Li / Li+ electrode potential under standard conditions,
[0021] p1 and p2 each independently refer to the number of sulfur atoms connected to the redox-active monomeric quinone moiety M1 and the monomeric quinone moiety M2, respectively, and the range of p1 and p2 each independently ranges from 1 to 5. When p1 is 1, S p1 is a sulfide, or when p1 is 2 to 5, S p1 For polysulfide,
[0022] When p2 is 1, S p2 is a sulfide, or when p2 is 2 to 5, S p2 For polysulfide,
[0023] m1 and m2 each independently range from 5 to 5,000, optionally the ratio of m1 to m2 ranges from 1:50 to 1:1, 1:20 to 1:2, 1:6 to 1:3, or 1:5 to 1:4,
[0024] The S-linked quinone copolymer of formula (II) has a weight average molecular weight ranging from 1,000 Daltons to 2,000,000 Daltons, and a solubility in tetrahydrofuran (THF) equal to or less than 1.0 microgram / mL at 21°C at 1 atmosphere.
[0025] According to a third aspect, a sulfided carbon matrix is described, wherein the sulfided carbon matrix is represented by formula (V), wherein Q is a bonded sp2 carbon atom (C) or nitrogen (N), wherein Indicates a single bond or a double bond, Sp represents a polysulfide and p ranges from 2 to 8, wherein the sulfided carbon matrix has a weight average MW ranging from 2000 Daltons to 2,000,000 Daltons,
[0026]
[0027] wherein the sulfurized carbon matrix has a sulfur content equal to or greater than 5 wt % and less than 20 wt %, equal to or greater than 20 wt % and less than 40 wt %, equal to or greater than 40 wt % and less than 60 wt %, equal to or greater than 60 wt % and less than 70 wt %, equal to or greater than 70 wt % and less than 80 wt %, based on the total weight of the sulfurized carbon matrix.
[0028] According to a fourth aspect, a redox-active composition is described that includes one or more S-linked quinone polymers described herein, one or more sulfided carbon matrices described herein, or any combination thereof, and an additive.
[0029] According to a fifth aspect, a redox-active composite material is described, the composite material comprising at least one S-linked quinone polymer as described herein and at least one sulfided carbon matrix as described herein.
[0030] According to a sixth aspect, a cathode material is described, wherein the cathode material comprises any redox-active composition and / or any redox-active composite material described herein. In particular, in some embodiments, the cathode material described herein comprises an S-linked quinone polymer selected from an S-linked quinone homopolymer, an S-linked quinone copolymer, and any combination thereof, and a sulfided carbon matrix described herein, wherein the weight ratio of the S-linked quinone polymer to the sulfided carbon matrix ranges from 20:1 to 1:20, 10:1 to 1:10, 9:1 to 3:2, or 6:1 to 2:1, or is 1:1.
[0031] According to a seventh aspect, a method and system for providing a cathode material are described. The method includes combining at least one S-connected quinone polymer described herein, at least one sulfurized carbon matrix or any combination thereof, and optionally an additive to provide a redox composition and / or a redox composite material configured to achieve sufficient contact with a non-aqueous electrolyte of an electrochemical cell and conductivity. The system includes at least one S-connected quinone polymer described herein, a sulfurized carbon matrix, and optionally an additive for use in combination to provide a cathode material according to the seventh aspect described herein.
[0032] According to an eighth aspect, a method and system for providing a cathode material is described herein. The method comprises
[0033] providing at least one S-linked quinone polymer selected from one or more S-linked quinone homopolymers, one or more S-linked quinone copolymers, and any combination thereof; and
[0034] At least one sulfurized carbon substrate is provided.
[0035] The method of providing a cathode material described herein also includes
[0036] At least one S-linked quinone polymer and at least one sulfided carbon matrix are combined to provide the cathode materials described herein.
[0037] The system includes
[0038] at least one S-linked quinone polymer selected from one or more S-linked quinone homopolymers, one or more S-linked quinone copolymers, and any combination thereof; and
[0039] at least one sulfided carbon matrix;
[0040] For use in combination in a method for providing a cathode material according to the eighth aspect described herein. In some embodiments, at least one S-connected quinone polymer and at least one sulfided carbon matrix are mixed together. In addition, or alternatively in some embodiments, at least one S-connected quinone polymer and at least one sulfided carbon matrix can be combined in any configuration that allows electrical connection between at least one S-connected quinone polymer and at least one sulfided carbon matrix, and when the cathode material is contained in an electrochemical cell, the configuration is capable of contacting with a non-aqueous electrolyte.
[0041] In preferred embodiments, the combination is performed to provide a cathode material as described herein, wherein the weight ratio of the S-linked quinone polymer to the sulfided carbon matrix ranges from 20:1 to 1:20, 10:1 to 1:10, 9:1 to 3:2, or 6:1 to 2:1, or is 1:1.
[0042] According to a ninth aspect, an electrochemical cell is described. The electrochemical cell comprises an anode, a cathode, and a non-aqueous electrolyte, wherein the cathode electrode comprises a cathode material as described herein. In a preferred embodiment, the anode comprises a lithium anode material, or a potassium anode material, or a sodium anode material, or a combination thereof, as will be understood by those skilled in the art.
[0043] In some embodiments, the cathode materials described include lithium and sodium, and the molar ratio of Li to Na ranges from 1:10 to 10:1, 4:6 to 6:4, or is 1:1.
[0044] In some embodiments, the cathode materials described include lithium and potassium, and the molar ratio of Li to K ranges from 1:10 to 10:1, 4:6 to 6:4, or is 1:1.
[0045] In some embodiments, the cathode materials described include sodium and potassium, and the molar ratio of Na to K ranges from 1:10 to 10:1, 4:6 to 6:4, or is 1:1.
[0046] According to a tenth aspect, an electrochemical cell is described herein, comprising an anode, a cathode, and a non-aqueous electrolyte, wherein the cathode electrode comprises one or more S-linked quinone polymers described herein, alone or in combination with a sulfided carbon matrix and / or a redox-active composite material described herein.
[0047] According to an eleventh aspect, methods and systems are described to provide an electrochemical cell as described herein. The method comprises combining an anode electrode with a cathode electrode, the cathode electrode comprising any cathode material as described herein, and in particular one or more S-linked quinone polymers as described herein, alone or in combination with a sulfided carbon matrix and / or a redox-active composite material as described herein.
[0048] The system includes any of the cathode materials described herein in combination with an anode material for combined use in a method of providing an electrochemical cell described herein.
[0049] In preferred embodiments of the method and system according to the eleventh aspect, the anode comprises a lithium material.
[0050] According to a twelfth aspect, a battery is described, comprising at least one electrochemical cell as described herein.
[0051] According to a thirteenth aspect, methods and systems for preparing S-linked quinone homopolymers are described.
[0052] The method includes
[0053] Providing redox-active monomers Quinone monomers X 1 -MX 2 , where X 1 and X 2 represents the leaving group,
[0054] Provide a sulfide Sp source,
[0055] Make the redox active monomer quinone monomer X 1 -MX 2 contacting with a sulfide Sp source under suitable conditions and for a sufficient period of time to provide an S-linked quinone polymer represented by formula (I)
[0056] -[MS p ]- m
[0057] (I)
[0058] in
[0059] M is a redox-active monomeric quinone moiety having a redox potential of 0.5 V to 3.5 V relative to the Li / Li+ electrode potential under standard conditions,
[0060] p refers to the number of sulfur atoms attached to the redox-active monomeric quinone moiety M, and p ranges from 1 to 5.
[0061] When p is 1, S p is a sulfide, or when p is 2 to 5, S p For polysulfide,
[0062] m ranges from 5 to 10,000,
[0063] wherein the S-linked quinone polymer has a weight average molecular weight of at least 1,000 Daltons and a solubility in tetrahydrofuran (THF) at 21° C. at 1 atmosphere of equal to or less than 1.0 microgram / mL.
[0064] The system comprises a redox-active monomer quinone monomer X 1 -MX 2 (Where X 1 and X 2 represents a leaving group) and a sulfide Sp source for combined use in the described method for preparing an S-linked quinone polymer.
[0065] According to a fourteenth aspect, a method and system for preparing an S-linked quinone copolymer is described. The method for preparing an S-linked quinone copolymer comprises
[0066] Providing redox-active monomers Quinone monomers X 1 -M1-X 2 and redox-active monomers quinone monomers X 1 -M2-X 2 , where X 1 and X 2 represents the leaving group,
[0067] Provide sulfide S p1 and S p2 The source,
[0068] Make the redox active monomer quinone monomer X 1 -M1-X 2 and redox-active monomers quinone monomers X 1 -M2-X 2 With sulfide S p1 and S p2The source of is contacted under suitable conditions and for a sufficient period of time to provide an S-linked quinone copolymer represented by formula (II)
[0069] -[M1-S p1 ] m1 -co-[M2-S p2 ]- m2
[0070] (II)
[0071] in
[0072] M1 and M2 are each a redox-active monomeric quinone moiety comprising a redox potential of 0.5 V to 3.5 V relative to the Li / Li+ electrode potential under standard conditions,
[0073] p1 and p2 each independently refer to the number of sulfur atoms connected to the redox-active monomeric quinone moiety M1 and the monomeric quinone moiety M2, respectively, and the range of p1 and p2 each independently ranges from 1 to 5. When p1 is 1, S p1 is a sulfide, or when p1 is 2 to 5, S p1 For polysulfide,
[0074] When p2 is 1, S p2 is a sulfide, or when p2 is 2 to 5, S p2 For polysulfide,
[0075] m1 and m2 each independently range from 5 to 5,000, optionally the ratio of m1 to m2 ranges from 1:50 to 1:1, 1:20 to 1:2, 1:6 to 1:3, or 1:5 to 1:4,
[0076] The S-linked quinone copolymer of formula (II) has a weight average molecular weight ranging from 1,000 Daltons to 2,000,000 Daltons, and a solubility in tetrahydrofuran (THF) equal to or less than 1.0 microgram / mL at 21°C at 1 atmosphere.
[0077] The system includes
[0078] -Redox-active monomers Quinone monomers X 1 -M1-X 2 and redox-active monomers quinone monomers X 1 -M2-X 2 , where X 1 and X 2 represents the leaving group, and
[0079] Sulfide S p1 and S p2 The source,
[0080] For use in combination in any of the described methods for preparing S-linked quinone copolymers.
[0081] In several embodiments, S-linked quinone polymers, sulfurized carbon matrices and related compositions, composites, electrode materials, electrodes, electrochemical cells, methods and systems allow for the provision of batteries with high capacity (at least 50 mAh / g for the active material or redox-active S-linked organosulfur polymer used), long life (e.g., at least 4 years) and / or low safety hazards (including low flammability) and low cost.
[0082] In several embodiments, the S-linked quinone polymers, sulfurized carbon matrices, and related compositions, composites, electrode materials, electrodes, electrochemical cells, methods, and systems described herein allow for the provision of batteries with low space usage and low replacement.
[0083] In several embodiments, the S-linked quinone polymers, sulfurized carbon matrices, and related compositions, composites, electrode materials, electrodes, electrochemical cells, methods, and systems described herein allow for the provision of batteries with higher capacity and longer life relative to existing polymer / metal and sulfur / metal batteries in non-aqueous electrolytes.
[0084] Furthermore, in several embodiments, the S-linked quinone polymers, sulfurized carbon matrices, and related compositions, composites, electrode materials, electrodes, electrochemical cells, methods, and systems described herein allow for the provision of Li batteries in non-aqueous electrolytes with comparable or higher capacity and longer life than existing batteries based on organic redox active materials.
[0085] The S-linked quinone polymers, sulfurized carbon matrices, and related composite materials, electrode materials, electrodes, electrochemical cells, methods, and systems described herein can be used in conjunction with applications where electrochemical cells with high capacity, long life, low safety hazards, low space usage, and / or low replacement are desired. Exemplary applications include, but are not limited to, batteries for electric vehicles, grid storage, telecommunications, and automotive start-stop.
[0086] The details of one or more embodiments of the present disclosure are set forth in the accompanying drawings and the description below. Other features and objects will be apparent from the description and drawings, and from the claims. BRIEF DESCRIPTION OF THE DRAWINGS
[0087] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate one or more embodiments of the present disclosure and, together with the description of the exemplary embodiments, explain the principles and implementations of the present disclosure.
[0088] Figure 1Exemplary S-linked organosulfur polymers (including PAQS, 36PPAQS, 27PPAQS, and PAQT) as cathode redox active materials, as well as a table of theoretical capacity (mAh / g), voltage vs. Li / Li+, and theoretical energy density (Wh / kg) in lithium batteries are shown. The molecular weights of these polymers range from 1,000 Da to 2,000,000 Da. As can be appreciated by the skilled artisan, the theoretical value takes into account the amount of charge that can be transferred per unit mass or volume by observing the basic electrochemical processes (number of electrons, voltage, mass) in the redox reaction.
[0089] Figure 2 The structures of the S-linked quinone polymers PAQS, 36PPAQS, 27PPAQS, PAQT and PBQS are shown. The molecular weights of these polymers range from 1,000 Da to 2,000,000 Da.
[0090] Figure 3 The structures of copolymers of PAQS or PAQT and PBQS are shown. The molecular weights of these polymers range from 1,000 Da to 2,000,000 Da.
[0091] Figure 4 Shows that it is possible to Figure 1 and Figure 2 The S-linked organosulfurquinone polymer combinations described in the present invention are used as a component of the structure of the sulfurized carbon matrix. SPAN (11), covalent triazine framework (S-CTF-1) (12), covalent triazine framework (SF-CTF-1) (13), poly (sulfur random-1,3-diisopropylbenzene) (poly (Sr-DIB)) (14), S-BOP (15), carbon / polymer sulfur (C / PS) composites (16), covalently grafted polysulfide graphene nanocomposites (PolySGN, 17), graphene-supported cross-linked sulfur copolymer nanoparticles, cp (STTCA) @ rGO-80 (18) are examples of sulfurized carbon matrices containing polymers, wherein S is present, for example, as CS, CSS, CSSS, CSSSS, CSSSSS-bonds, as will be understood by the skilled person upon reading the present disclosure.
[0092] Figure 5 The voltage curve (charge and discharge characteristics) of a Li / / 36PPAQS cell in ANA-6 at C / 10 is shown. C is the capacity of the cell, (discharge) charge for n hours makes C / n = full capacity for (discharge) charge for n hours, so C / 10 = full capacity for discharge (or charge) for 10 hours.
[0093] Figure 6The cycling characteristics of Li / / 36PPAQS single cells in ANA-6 at C / 10 are shown.
[0094] Figure 7 The Coulombic efficiency vs. cycle number curve of Li / / 36PPAQS single cell in ANA-6 is shown.
[0095] Figure 8 The voltage curves (charge and discharge characteristics) of a Li / / PAQT cell in ANA-7 at C / 10 are shown.
[0096] Fig. 9 The cycling characteristics of Li / / PAQT single cells in ANA-7 at C / 10 are shown.
[0097] Fig.10 The Coulombic efficiency vs. cycle number curves of Li / / PAQT single cells in ANA-7 are shown.
[0098] Fig.11 The voltage curves (charge and discharge characteristics) of a Li / / PAQS:SPAN single cell in ANA-4 at C / 10 are shown.
[0099] Fig.12 Shown are the discharge capacity vs. cycle number of Li / / PAQS:SPAN cells in ANA-4 at C / 10.
[0100] Fig.13 Shown is the Coulombic efficiency vs. cycle number of Li / / PAQS:SPAN single cells in ANA-4 at C / 10.
[0101] Fig.14 Shown is the energy density (kWh / g) vs. cycle number of Li / / PAQS:SPAN cells in ANA-4 at C / 10.
[0102] Fig.15 The voltage curves (charge and discharge characteristics) of a Li / / PAQS:SPAN (48:38) single cell in ANA-6 at C / 10 are shown.
[0103] Fig.16 Shown are the discharge capacity vs. cycle number of Li / / PAQS:SPAN (48:38) cells in ANA-6 at C / 10.
[0104] Fig.17 Shown is the coulombic efficiency vs. cycle number of Li / / PAQS:SPAN (48:38) single cells in ANA-6 at C / 10.
[0105] Fig.18The voltage curves (charge and discharge characteristics) of a Li / / PAQS:SPAN (70:20) single cell in ANA-4 at C / 10 are shown.
[0106] Fig.19 Shown are the discharge capacity vs. cycle number of Li / / PAQS:SPAN (70:20) cells in ANA-4 at C / 10.
[0107] Fig. 20 Shown is the coulombic efficiency vs. cycle number of Li / / PAQS:SPAN (70:20) single cells in ANA-4 at C / 10.
[0108] Fig.21 The voltage curves (charge and discharge characteristics) of the Li / / PAQS0.8-PBQS0.2 single cell in ANA-4 at C / 10 are shown.
[0109] Fig. 22 Shown are the discharge capacity vs. cycle number of Li / / PAQS0.8-PBQS0.2 single cells in ANA-4 at C / 10.
[0110] Fig.23 Shown is the Coulombic efficiency vs. cycle number of Li / / PAQS0.8-PBQS0.2 single cells in ANA-4 at C / 10.
[0111] Fig.24 The voltage curves (charge and discharge characteristics) of a Li / / PAQS:SC single cell in ANA-4 at C / 10 are shown.
[0112] Fig.25 Shown are the discharge capacity vs cycle number of Li / / PAQS:SC cells in ANA-4 at C / 10.
[0113] Fig.26 Coulombic efficiency vs cycle number of Li / / PAQS:SC single cells in ANA-4 at C / 10 are shown.
[0114] Fig. 27 The voltage curves (charge and discharge characteristics) of a Li / / PAQS:S single cell in ANA-4 at C / 10 are shown.
[0115] Fig.28 Shown are the discharge capacity vs cycle number of Li / / PAQS:S cells in ANA-4 at C / 10.
[0116] Fig.29 Coulombic efficiency vs cycle number of Li / / PAQS:S single cells in ANA-4 at C / 10 are shown.
[0117] Fig.30 The element S(S 8 ) and sulfurized polyacrylonitrile (SPAN) structure comparison.
[0118] Fig.31 The figure above shows a schematic diagram of an exemplary electrochemical cell including a Li anode and a cathode comprising an organosulfur polymer described herein. Fig.31 The figure below shows a schematic diagram of an exemplary pouch case electrochemical cell including a Li anode and a cathode comprising a tricyclic compound described herein.
[0119] Fig.32 An exemplary arrangement of a plurality of electrochemical cells in a battery as described herein is shown.
[0120] Fig.33 A schematic diagram of an exemplary plurality of electrically connected electrochemical cells according to the present disclosure is shown.
[0121] Fig.34 The voltage curves (charge and discharge characteristics) of a Li / / Gen4 single cell in ANA-42 at C / 10 are shown.
[0122] Fig.35 Shown are the discharge capacity (mAh / g) vs. cycle number of Li / / Gen4 cells in ANA-42 at C / 10.
[0123] Fig.36 Shown is the coulombic efficiency vs cycle number of Li / / Gen4 cells in ANA-42 at C / 10.
[0124] Fig.37 Shown are the energy density (mAh / g) vs. cycle number of Li / / Gen4 cells in ANA-42 at C / 10.
[0125] Fig.38 The voltage curves (charge and discharge characteristics) of a Li / / Gen4 single cell in ANA-42 at C / 3 are shown.
[0126] Fig.39 Shown is the discharge capacity (mAh / g) vs. cycle number of Li / / Gen4 cells in ANA-42 at C / 3.
[0127] Fig.40 Coulombic efficiency vs cycle number of Li / / Gen4 cells in ANA-42 at C / 3 is shown.
[0128] Fig.41The voltage curves (charge and discharge characteristics) of a Li / / Gen5 single cell in ANA-42 at C / 10 are shown.
[0129] Fig.42 Shown are the discharge capacity (mAh / g) vs. cycle number of Li / / Gen5 cells in ANA-42 at C / 10.
[0130] Fig.43 Shown is the coulombic efficiency vs cycle number of Li / / Gen5 cells in ANA-42 at C / 10.
[0131] Fig.44 The Li / / PAQS in ANA-5 at C / 10 is shown. 0.8 -PBQS 0.2 Voltage curve (charge and discharge characteristics) of a single battery.
[0132] Fig.45 The Li / / PAQS in ANA-5 at C / 10 is shown. 0.8 -PBQS 0.2 Discharge capacity of a single cell vs. number of cycles. DETAILED DESCRIPTION
[0133] Described herein are S-linked quinone polymers, sulfurized carbon-based polymers, and related compositions, electrode materials, electrodes, electrochemical cells, batteries, methods, and systems.
[0134] As used herein, the term "S-linked quinone polymer" refers to a sulfur-containing quinone polymer in which the monomer units are linked by sulfur (-S-) bonds. Thus, an S-linked quinone polymer is a sulfur-containing polymer comprising one or more redox-active quinone moieties, as will be understood by the skilled artisan.
[0135] The term "polymer" as used herein refers to any class of natural or synthetic substances composed of very large organic molecules (called macromolecules) that include many repeating identical and / or different chemical units (called monomers). In particular, the term "polymer" includes any product produced by organic repeating units connected by covalent chemical bonds, the organic repeating units including, for example, aromatic moieties such as benzene, naphthalene, anthracene and moieties derivable therefrom such as quinones, and aliphatic monomer units such as ethylene, propylene, cyclooctadiene, dienes, olefins, acrylonitrile, methyl methacrylate, vinyl acetate, dichlorodimethylsilane, tetrafluoroethylene, and other monomers identifiable to the skilled person. Monomers as described herein may include substituents selected from the following: F, Cl, Br, I, CF3, linear or branched, substituted or unsubstituted C1-C4 aliphatic groups, aromatic, heteroaromatic, non-aromatic rings, or non-aromatic heterocyclic rings containing substituents containing 4 to 12 carbon atoms and 0 to 4 heteroatoms, or any suitable substituents identifiable to the skilled person.
[0136] Thus, S-linked quinone polymers as described herein comprise polymers in the sense of the present disclosure which in turn comprise redox active quinone monomer moieties.
[0137] As used herein, the term "redox active" refers to a chemical moiety (e.g., a polymer or monomer or portion thereof) that can be reversibly oxidized or reduced in a non-aqueous electrolyte to produce a detectable redox potential. Redox active functional groups include ketones, aldehydes and carboxylic acids, imines, organosulfides, and additional functional groups that can be recognized by the skilled artisan.
[0138] In the S-linked quinone polymers described herein, the redox active moiety has a redox potential of 0.50 V to 3.5 V relative to the Li / Li+ electrode potential under standard conditions. It should be understood that those skilled in the art will know that Li / Li + With a potential of -3.04 V relative to SHE, the + The potential of the redox part relative to Li / Li is obtained by subtracting 3.04 V from the potential of + The potential of the redox part is converted to the potential of the redox part relative to the SHE.
[0139] Thus, the S-linked quinone polymers described herein have charge capabilities, as will be understood by the skilled artisan. As used herein, the term "charge capacity" is a measure of the product of the current multiplied by the time the anode material accepts a charge until the cutoff voltage is reached. The discharge capacity is the product of the current multiplied by the time the cathode material accepts a charge until the cutoff voltage is reached.
[0140]
[0141] Where Q is the theoretical capacity,
[0142] n is the number of electrons exchanged,
[0143] F is Faraday's constant, and
[0144] MW is the molecular weight of the electroactive material.
[0145] Since the redox potential in the S-linked quinone polymers described herein is 0.5 V to 3.5 V relative to the Li / Li+ electrode potential, in order to increase or decrease the redox potential of the starting redox-active monomer portion, the substituent group can be selected based on the Hammett σ constant, such as the constant shown in Table 1 below.
[0146] Since the redox potential in the S-linked quinone polymers described herein is 0.50 V to 3.5 V relative to the Li / Li+ electrode potential, in order to increase or decrease the redox potential of the starting redox-active monomer portion, the substituent group can be selected based on the Hammett σ constant, such as the constant shown in Table 1 below.
[0147]
[0148]
[0149] *σmeta, σpara = Hammett constant; σI = inductance σ constant; σv = Charton's v (size) value; p = hydrophobicity parameter; Es = Taft size parameter; MR = molar refractive index (polarizability) parameter.
[0150] **Indicates that the group is in the most sterically hindered conformation.
[0151] For example, to increase the redox potential of a starting redox-active monomer moiety having an aromatic ring, the relevant Hammett σ constant may include CN or CF 3 The skilled artisan, upon reading this disclosure, will appreciate additional modifications to increase or decrease the redox potential of the starting moiety.
[0152] In some embodiments of the S-linked quinone polymers described herein, the redox-active moiety is provided by the quinone portion of the polymer.
[0153] As used herein, the term "quinone" and related moieties refer to a class of organic compounds that are formally "derived from aromatic compounds [such as benzene or naphthalene] by converting an even number of -CH= groups to -C(=O)- groups and carrying out any necessary rearrangement of double bonds to produce a "completely conjugated cyclic diketone structure" [1] [2] [3] [4] [5]. Exemplary quinones include moieties such as 1,4-benzoquinone or cyclohexadienedione, often referred to simply as "quinone" (hence the name of the class). Other examples are 1,2-benzoquinone (o-quinone), 1,4-naphthoquinone, and 9,10-anthraquinone [5]. Other quinones include 2,5-dichloroanthraquinone, 3,6-dibromo-phenanthrenequinone, 2,7-dibromo-phenanthrenequinone, and 1,2,5,6-anthracenetetrone as described herein, as well as additional quinones that will be appreciated by the skilled artisan.
[0154] In some embodiments described herein, S-linked quinone polymers include homopolymers of 2,5-S-linked anthraquinone (PAQS), 3,6-S-linked phenanthrenequinone (36PPAQS), 2,7-S-linked phenanthrenequinone (27PPAQS), and 9,10-S-linked 1,2,5,6-anthracentetraone (PAQT) as described herein, as well as copolymers in configurations such as alternating copolymers, random copolymers, block copolymers, and graft copolymers, as will be understood by the skilled artisan. An exemplary random copolymer as described herein is polyanthraquinone-benzoquinone sulfide (PAQS-BQ) of Example 34. Additional quinone copolymers are identifiable to the skilled artisan in the sense of the present disclosure.
[0155] In some embodiments, by reacting chlorinated or brominated quinone monomers with Na 2 The reaction of S at 120°C to 150°C yields an S-linked polymer.
[0156] In some embodiments, the S-linked quinone polymer of the present disclosure may be an S-linked homopolymer represented by formula (I):
[0157] -[MS p ]- m
[0158] (I)
[0159] in
[0160] M is a redox-active monomeric quinone moiety comprising a redox potential of 0.5 V to 3.5 V relative to the Li / Li+ electrode potential under standard conditions,
[0161] p refers to the number of sulfur atoms attached to the redox-active monomeric quinone moiety M, and p ranges from 1 to 5.
[0162] When p is 1, S p is a sulfide, or when p is 2 to 5, Sp For polysulfide,
[0163] m ranges from 5 to 10,000,
[0164] wherein the S-linked quinone polymer has a weight average molecular weight of at least 1,000 Daltons and a solubility in tetrahydrofuran (THF) at room temperature (i.e., 21° C.) at 1 atmosphere of pressure of 1.0 μg / mL or less, preferably a solubility in tetrahydrofuran (THF) at room temperature at 1 atmosphere of pressure of 0.1 μg / mL or less, and more preferably a solubility in tetrahydrofuran (THF) at room temperature at 1 atmosphere of pressure of 0.01 μg / mL or less.
[0165] In some embodiments, at least one redox-active monomeric moiety M of formula (I) can be represented by formula (III):
[0166]
[0167] Where R 1 , R 2 , R 3 and R 4 Each independently empty; H; S p , wherein p ranges from 1 to 5; F; Cl; Br; I; CF3; a linear or branched, substituted or unsubstituted C1-C4 aliphatic group, an aromatic, heteroaromatic, non-aromatic ring; or a non-aromatic heterocyclic ring containing substituents containing 4 to 12 carbon atoms and 0 to 4 heteroatoms,
[0168] The heteroatom is selected from O, N and S, R 1 and R 2 Together and / or R 3 and R 4 together are part of an aromatic or aliphatic cyclic structure, and wherein when the associated R 1 , R 2 , R 3 or R 4 When empty, the dashed line ----- represents empty or a single bond to the quinone ring carbon.
[0169] In some embodiments, the at least one redox-active monomeric moiety M of formula (I) represented by formula (III) can be any one of the S-linked monomeric moieties -SM of formula (IIIA) and formula (IIIB)
[0170]
[0171] In some embodiments, at least one redox-active monomeric moiety M of formula (I) can be represented by formula (IV):
[0172]
[0173] Where R 1 , R 2 , R 3 and R 4 Each independently empty; H; S p , wherein p ranges from 1 to 5; F; Cl; Br; I; CF3; a linear or branched, substituted or unsubstituted C1-C4 aliphatic group; an aromatic, heteroaromatic, non-aromatic ring; or a non-aromatic heterocyclic ring containing substituents containing 4 to 12 carbon atoms and 0 to 4 heteroatoms,
[0174] The heteroatom is selected from O, N and S, R 1 and R 2 Together and / or R 3 and R 4 together are part of an aromatic or aliphatic cyclic structure, and wherein when the associated R 1 , R 2 , R 3 or R 4 When empty, the dashed line ----- represents empty or a single bond to the quinone ring carbon.
[0175] In some embodiments, the at least one redox-active monomeric moiety M of formula (I) represented by formula (IV) can be any of the S-linked monomeric moieties shown in formula (IVA), formula (IVB), formula (IVC)
[0176]
[0177] In some embodiments, the sulfide Sp source includes but is not limited to elemental sulfur S8, Na 2 S. Li 2 S.K. 2 S, any other sulfur-containing compound known to the skilled person.
[0178] In some embodiments, the S-linked quinone polymer of the present disclosure may be an S-linked copolymer represented by formula (II):
[0179] -[M1-S p1 ] m1 -co-[M2-S p2 ]- m2
[0180] (II)
[0181] in
[0182] M1 and M2 are each a redox-active monomeric quinone moiety comprising a redox potential of 0.5 V to 3.5 V relative to the Li / Li+ electrode potential under standard conditions,
[0183] p1 and p2 each independently refer to the number of sulfur atoms attached to the redox-active monomeric quinone moieties M1 and M2, respectively, and p1 and p2 each independently range from 1 to 5,
[0184] When p1 is 1, S p1 is a sulfide, or when p1 is 2 to 5, S p1 For polysulfide,
[0185] When p2 is 1, S p2 is a sulfide, or when p2 is 2 to 5, S p2 For polysulfide,
[0186] m1 and m2 each independently range from 5 to 5,000, optionally the ratio of m1 to m2 ranges from 1:50 to 1:1, 1:20 to 1:2, 1:6 to 1:3 or 1:5 to 1:4,
[0187] The S-linked quinone copolymer of formula (II) has a weight average molecular weight of at least 1,000 Daltons and a solubility in tetrahydrofuran (THF) of 1.0 μg / mL or less at room temperature at 1 atmosphere, preferably a solubility in tetrahydrofuran (THF) of 0.1 μg / mL or less at room temperature at 1 atmosphere, more preferably a solubility in tetrahydrofuran (THF) of 0.01 μg / mL or less at room temperature at 1 atmosphere.
[0188] Formula (II) represents any arrangement of the M1 and M2 moieties in an S-linked copolymer, including random copolymers, block copolymers, and alternating copolymers.
[0189] In particular, in some embodiments, the redox-active monomers M1 and M2 in the S-linked copolymer can be statistical random copolymers, wherein the redox-active monomers M1 and M2 are statistically randomly present in the network polymer. An exemplary statistical random copolymer of M1 and M2 can be represented as
[0190] -M1-S-M2-S-M1-S-M2-S-M1-S-M1-S-M2-S-M1-S-M2-S-M2-S-
[0191] In some embodiments, a method for preparing an S-linked quinone copolymer is described. The method comprises
[0192] Providing redox-active monomers Quinone monomers X1 -M1-X 2 and redox-active monomers quinone monomers X 1 -M2-X 2 , where X 1 and X 2 represents the leaving group,
[0193] Provide sulfide S p1 and S p2 The source,
[0194] Make the redox active monomer quinone monomer X 1 -M1-X 2 and redox-active monomers quinone monomers X 1 -M2-X 2 With sulfide S p1 and S p2 The source of is contacted under suitable conditions and for a sufficient period of time to provide an S-linked quinone copolymer represented by formula (II)
[0195] -[M1-S p1 ] m1 -co-[M2-S p2 ]- m2
[0196] (II)
[0197] in
[0198] M1 and M2 are each a redox-active monomeric quinone moiety comprising a redox potential of 0.5 V to 3.5 V relative to the Li / Li+ electrode potential under standard conditions,
[0199] p1 and p2 each independently refer to the number of sulfur atoms connected to the redox-active monomeric quinone moiety M1 and the monomeric quinone moiety M2, respectively, and p1 and p2 each independently range from 1 to 5,
[0200] When p1 is 1, S p1 is a sulfide, or when p1 is 2 to 5, S p1 For polysulfide,
[0201] When p2 is 1, S p2 is a sulfide, or when p2 is 2 to 5, S p2 For polysulfide,
[0202] m1 and m2 each independently range from 5 to 5,000, optionally the ratio of m1 to m2 ranges from 1:50 to 1:1, 1:20 to 1:2, 1:6 to 1:3, or 1:5 to 1:4,
[0203] The S-linked quinone copolymer of formula (II) has a weight average molecular weight ranging from 1,000 Daltons to 2,000,000 Daltons, and a solubility in tetrahydrofuran (THF) equal to or less than 1.0 microgram / mL at 21°C at 1 atmosphere.
[0204] In some embodiments, the leaving groups X1 and X2 can be independently selected from Cl - Br – ,I - , - OTs, - OMs, – OTf or any other leaving group known to the skilled person.
[0205] In some embodiments, the sulfide S p1 and S p2 The sources include but are not limited to elemental sulfur S8, Na 2 S. Li 2 S.K. 2 S, any other sulfur-containing compound known to the skilled person.
[0206] In some embodiments, the redox-active monomer M1 and the redox-active monomer M2 in the S-linked copolymer may be an alternating copolymer, wherein the redox-active monomer M1 and the redox-active monomer M2 are alternately present in the S-linked copolymer. An exemplary alternating S-linked copolymer of M1 and M2 may be represented as
[0207] -M1-S-M2-S-M1-S-M2-S-M1-S-M2-S-M1-S-M2-S-M1-S-M2-S.
[0208] In some embodiments, the redox-active monomers M1 and M2 in the S-linked copolymer can be M1M2 diblock copolymers, wherein the redox-active monomers M1 and M2 are present in the S-linked copolymer only in a sequence of at least 5 moieties. An exemplary M1M2 diblock S-linked copolymer of M1 and M2 can be represented as
[0209] -M1-S-M1-S-M1-S-M1-S-M1-S-M1-S-M2-S-M2-S-M2-S-M2-S-M2-S-M2-S-.
[0210] In some embodiments, the redox-active monomer M1, the redox-active monomer M2 in the S-linked copolymer represents a M1M2M1 triblock copolymer, wherein one of the redox-active monomer M1 and the redox-active monomer M2 is present in at least two sequences of at least 5 moieties separated by sequences of different moieties in the network polymer. An exemplary M1M2 triblock copolymer of M1 and M2 can be represented as
[0211] -M1-S-M1--M1-S-M1-S-M1-S-M2-S-M2-S-M2-S-M2-S-M2-S-M1-S-M1-SMS-M1-S-M1-S-M1-S-.
[0212] In some embodiments, the redox-active monomeric quinone moiety M1 and the redox-active monomeric quinone moiety M2 of formula (II) can be independently represented by any one of formula (III) and formula (IIV):
[0213]
[0214] Where R 1 , R 2 , R 3 and R 4 each independently empty; H; Sp, where p ranges from 1 to 5; F; Cl; Br; I; CF3; a linear or branched, substituted or unsubstituted C1-C4 aliphatic group; an aromatic, heteroaromatic, non-aromatic ring; or a non-aromatic heterocyclic ring containing substituents containing 4 to 12 carbon atoms and 0 to 4 heteroatoms,
[0215] The heteroatom is selected from O, N and S, R 1 and R 2 Together and / or R 3 and R 4 together are part of an aromatic or aliphatic ring structure, and
[0216] When the relevant R 1 , R 2 , R 3 or R 4 When empty, the dashed line ----- represents empty or a single bond to the quinone ring carbon.
[0217] In some embodiments, the S-linked redox-active monomeric quinone moiety-S-M1 and the S-linked redox-active monomeric quinone moiety-S-M2 of formula (II) can independently be any of the S-linked monomeric moiety-SM of formula (IIIA), formula (IIIB), formula (IVA), formula (IVB), and formula (IVC)
[0218]
[0219] In some embodiments, the S-linked copolymer comprises an S-linked redox-active monomeric quinone moiety -S-M1 of formula (IIIA) S-linked monomeric moiety -SM,
[0220]
[0221] and an S-linked redox-active monomeric quinone moiety -S-M of formula (II) or any of the S-linked monomeric moieties -SM of formula (IIIB), formula (IVA), formula (IVB), and formula (IVC),
[0222]
[0223] wherein the molar ratio of the S-linked monomer moiety -S-M1 of formula (IIIA) to the S-linked monomer moiety -S-M2 of formula (IIIB), formula (IVA), formula (IVB) or formula (IVC) ranges from 1:50 to 1:1, 1:20 to 1:2, 1:6 to 1:3 or 1:5 to 1:4, or
[0224] The molar ratio of the S-linked monomer moiety -S-M1 of formula (IIIA) to the S-linked monomer moiety -S-M2 of formula (IIIB), formula (IVA), formula (IVB) or formula (IVC) can be 1:4.
[0225] In some embodiments, the S-linked copolymer as described comprises a redox-active monomeric quinone moiety M1 of formula (II) and a redox-active monomeric quinone moiety M2, which can be independently represented by formula (III):
[0226]
[0227] Where R 1 , R 2 , R 3 and R 4 Each independently empty; H; S p , wherein p ranges from 1 to 5; F; Cl; Br; I; CF3; a linear or branched, substituted or unsubstituted C1-C4 aliphatic group; an aromatic, heteroaromatic, non-aromatic ring; or a non-aromatic heterocyclic ring containing substituents containing 4 to 12 carbon atoms and 0 to 4 heteroatoms,
[0228] The heteroatom is selected from O, N and S, R 1 and R 2 Together and / or R 3 and R 4 together are part of an aromatic or aliphatic cyclic structure, and wherein when the associated R 1 , R2 , R 3 or R 4 When empty, the dashed line ----- represents empty or a single bond to the quinone ring carbon.
[0229] In some embodiments, the S-linked redox-active monomeric quinone moiety-S-M1 and the S-linked redox-active monomeric quinone moiety-S-M2 of formula (II) can be the S-linked monomeric moiety-SM of formula (IIIA) and formula (IIIB).
[0230]
[0231] wherein the molar ratio of the S-linked monomer moiety -S-M1 of formula (IIIA) to the S-linked monomer moiety -S-M2 of formula (IIIB) ranges from 1:50 to 1:1, 1:20 to 1:2, 1:6 to 1:3, or 1:5 to 1:4.
[0232] In some embodiments, redox-active S-linked copolymer PAQS is described. 0.8 BQ 0.2 , wherein the S-linked redox-active monomeric quinone moiety-S-M1 and the S-linked redox-active monomeric quinone moiety-S-M2 of formula (II) can independently be any one of the S-linked monomeric moiety-SM of formula (IIIA) and formula (IIIB)
[0233]
[0234] The molar ratio of the S-linked monomer moiety -SM of formula (IIIA) to that of formula (IIIB) may be 1:4.
[0235] In some embodiments, the redox-active monomeric quinone moiety M1 and the redox-active monomeric quinone moiety M2 of formula (II) may be represented by formula (IV):
[0236]
[0237] Where R 1 , R 2 , R 3 and R 4 Each independently empty; H; S p , wherein p ranges from 1 to 5; F; Cl; Br; I; CF3; a linear or branched, substituted or unsubstituted C1-C4 aliphatic group; an aromatic, heteroaromatic, non-aromatic ring; or a non-aromatic heterocyclic ring containing substituents containing 4 to 12 carbon atoms and 0 to 4 heteroatoms,
[0238] The heteroatom is selected from O, N and S, R 1 and R2 Together and / or R 3 and R 4 together are part of an aromatic or aliphatic cyclic structure, and wherein when the associated R 1 , R 2 , R 3 or R 4 When empty, the dashed line ----- represents empty or a single bond to the quinone ring carbon.
[0239] In some embodiments, the S-linked redox-active monomeric quinone moiety-S-M1 and the S-linked redox-active monomeric quinone moiety-S-M2 of formula (II) represented by formula (IV) can be any of the S-linked monomeric moieties shown in formula (IVA), formula (IVB), formula (IVC)
[0240]
[0241] In some embodiments, one or more S-linked polymers described herein are included in a composite material, alone or in various combinations recognizable to a skilled artisan, along with one or more sulfurized carbon matrices.
[0242] As used herein, the term "sulfided carbon matrix" or "sulfur-incorporated carbon matrix" refers to a carbon-based matrix in which elemental sulfur is embedded in a carbon-based matrix, wherein the elemental sulfur is connected to the C atoms of the matrix material in structures such as CS, CSS, CSSS, CSSSS, CSSSSS bonds or other higher polysulfide structures. As used herein, the term "carbon matrix" refers to a solid carbon-based material in which the inorganic graphite or organic monomer portion of the polymer matrix is configured to be connected to C atoms, Group 16 elements, and particularly S in the form of CS, CSS, CSSS, CSSSS, CSSSSS bonds within the surrounding organic matter as described herein. For example, any configuration of aromatic monomers connected to each other in any configuration as described herein results in the presence of CS, CSS, CSSS, CSSSS, CSSSSS bonds on the resulting organic portion for electrochemical reactions with other molecules or compounds such as electrolytes and / or S-linked polymers described herein. Exemplary carbon-based matrices include graphite, polyacrylonitrile, and other carbon-based matrices as will be understood by the skilled artisan.
[0243] The sulfided carbon matrix described herein can be provided by sulfiding elemental sulfur at high temperature in the presence of a polymer comprising aromatic moieties to form a carbon-based matrix, wherein the sulfur atoms are incorporated into the matrix and carbonized at a suitable temperature, which can be, for example, >300°C, and preferably >500°C, or in the range of 300°C to 1000°C, or 500°C to 800°C.
[0244] Based on the reversible breaking and formation of disulfide (S--S) bonds, carbon matrices incorporating sulfur can provide relatively high theoretical capacities. Three types of organosulfur cathodes are being used: (i) small organosulfur molecules, (ii) high-sulfur polymers, and (iii) sulfided polymers. Small organosulfur molecules are soluble in organic electrolytes, so their use as cathode active materials is limited. High-sulfur polymers and sulfided polymers are insoluble in organic solvents, but they still form small amounts of soluble polysulfides during deep discharge, so such soluble sulfides are overcharged during the charging process due to the shuttle mechanism. Although significant progress has been made in recent years in realizing organosulfur polymers as cathode active materials for practical batteries, major obstacles need to be overcome due to the shuttle effect, high electrolyte loading, high conductive carbon loading, and low tap density.
[0245] In some embodiments, the sulfur-incorporated carbon matrix may be SPAN (sulfurized poly[acrylonitrile]): a sulfurized carbon matrix polymer of elemental sulfur and polyacrylonitrile that exhibits high capacity (>200 mAh / g from 3.0 V to 0.500 V) and better cycling stability than a standard sulfur cathode in an electrochemical cell with a lithium anode; however, most of the capacity is obtained at lower potentials (e.g., below 2.0 V) than conventional Li / S cells, making it less preferred than Li / S compositions. The total S content in SPAN is ˜30% to 50%, and its capacity may vary between 300 and 800 mAh / g SPAN. As will be appreciated by the skilled artisan, these features may be found in other sulfurized carbon matrix polymers that may have a total S content of ˜30 wt / wt% to 50 wt / wt% relative to the total weight of the sulfurized carbon matrix polymer and a capacity varying between 300 and 800 mAh / g active polymer.
[0246] In some embodiments, the redox-active composite material as described herein comprises a sulfided carbon matrix represented by formula (V), wherein Q is a bonded sp2 carbon atom (C) or nitrogen (N), wherein Indicates a single bond or a double bond, S prepresents a polysulfide and p ranges from 2 to 8, wherein the weight average MW of the sulfided carbon matrix ranges from 2000 Daltons to 2,000,000 Daltons, 10,000 Daltons to 1,500,000 Daltons, 100,000 Daltons to 1,000,000 Daltons,
[0247]
[0248] In some embodiments, the sulfurized carbon matrix has a sulfur content equal to or greater than 5 wt% and less than 20 wt%, equal to or greater than 20 wt% and less than 40 wt%, equal to or greater than 40 wt% and less than 60 wt%, equal to or greater than 60 wt% and less than 70 wt%, equal to or greater than 70 wt% and less than 80 wt%, based on the total weight of the sulfurized carbon matrix.
[0249] In some embodiments, a redox-active composite material as disclosed herein comprises a sulfided carbon matrix represented by formula (V), wherein Q is N.
[0250] In some embodiments, a redox-active composite material as disclosed herein comprises a sulfided carbon matrix represented by formula (V), wherein Q is C.
[0251] In some embodiments, the sulfided carbon matrix of formula (V) may be selected from Figure 4 Any of the examples shown in , including sulfurized carbon matrix polymer SPAN (11), covalent triazine framework (S-CTF-1) (12), covalent triazine framework (S-CTF-1) (13), poly (sulfur random-1,3-diisopropylbenzene) (poly (Sr-DIB) (14), S-BOP (15), carbon / polymer sulfur (C / PS) composites (16), covalently grafted polysulfide graphene nanocomposites (PolySGN, 17) and graphene-supported cross-linked sulfur copolymer nanoparticles cp (S-TTCA) @ rGO-80 (18) or any combination thereof.
[0252] In some embodiments, a redox-active composite material as disclosed herein comprises an S-linked quinone polymer represented by formula (I):
[0253] -[MS p ]- m
[0254] (I)
[0255] in
[0256] M is a redox-active monomeric quinone moiety comprising a redox potential of 0.5 V to 3.3 V relative to the Li / Li+ electrode potential under standard conditions,
[0257] p refers to the number of sulfur atoms attached to the redox-active monomeric quinone moiety M, and p ranges from 1 to 5.
[0258] When p is 1, S p is a sulfide, or when p is 2 to 5, S p For polysulfide,
[0259] m ranges from 5 to 10,000,
[0260] wherein the S-linked quinone polymer has a weight average molecular weight of at least 1500 Daltons or a weight average MW ranging from 2000 Daltons to 2,000,000 Daltons, 10,000 to 1,500,000 Daltons, 100,000 to 1,000,000 Daltons, and a solubility in tetrahydrofuran (THF) equal to or less than 1.0 microgram / mL at room temperature at 1 atmosphere, preferably a solubility in tetrahydrofuran (THF) equal to or less than 0.1 microgram / mL at room temperature at 1 atmosphere, more preferably a solubility in tetrahydrofuran (THF) equal to or less than 0.01 microgram / mL at room temperature at 1 atmosphere, and a sulfurized polymer represented by formula (V), wherein Q is a bonded sp2 carbon atom (C) or nitrogen (N), wherein Indicates a single bond or a double bond, S p represents a polysulfide and p ranges from 2 to 8, wherein the sulfurized polymer has a weight average MW of at least 2000, 10,000, 100,000 or 1,000,000 or a weight average MW ranging from 2000 Daltons to 2,000,000 Daltons, 10,000 Daltons to 1,500,000 Daltons, 100,000 Daltons to 1,000,000 Daltons,
[0261]
[0262] wherein the weight ratio of the S-linked quinone polymer represented by formula (I) to the sulfurized polymer represented by formula (V) ranges from 20:1 to 1:20, 10:1 to 1:10, 9:1 to 3:2, or 6:1 to 2:1.
[0263] In some embodiments, the redox active material as described herein further comprises a binder and a conductive additive, wherein the binder is selected from one of poly(vinylidene fluoride), poly(tetrafluoroethylene), sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, potassium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid (PAA), polyvinyl alcohol (PVA), polyethylene glycol (PEG), polyethylene oxide (PEO), polyamideimide (PAI), or any combination thereof, and wherein the conductive additive is selected from one of graphite, carbon black, acetylene black, Super-P carbon, graphite, carbon nanotubes, vapor-grown carbon fibers, graphene, nickel powder, KB, and SP65, or any combination thereof.
[0264] As used herein, a conductive additive is a solid material that, when present in an electrode composition, enhances the conductivity of the resulting electrode composition.
[0265] In some embodiments, in a redox active composite as described herein, the binder is present at 1% to 20% by weight of the total electrode composition and the conductive additive is present at 5% to 70% by weight of the total electrode composition.
[0266] In some embodiments, a redox-active composite material as disclosed herein comprises an S-linked quinone copolymer represented by formula (II)
[0267] -[M1-S p1 ] m1 -co-[M2-S p2 ]- m2
[0268] (II)
[0269] in
[0270] M1 and M2 are each a redox-active monomeric quinone moiety comprising a redox potential of 0.5 V to 3.5 V relative to the Li / Li+ electrode potential under standard conditions,
[0271] p1 and p2 each independently refer to the number of sulfur atoms attached to the redox-active monomeric quinone moieties M1 and M2, respectively, and p1 and p2 each independently range from 1 to 5,
[0272] When p1 is 1, S p1 is a sulfide, or when p1 is 2 to 5, S p1 For polysulfide,
[0273] When p2 is 1, S p2 is a sulfide, or when p2 is 2 to 5, S p2 For polysulfide,
[0274] m1 and m2 each independently range from 5 to 5,000, optionally the ratio of m1 to m2 ranges from 1:50 to 1:1, 1:20 to 1:2, 1:6 to 1:3 or 1:5 to 1:4,
[0275] wherein the S-linked quinone copolymer of formula (II) has a weight average molecular weight of at least 1000 Daltons or a weight average MW ranging from 2000 Daltons to 2,000,000 Daltons, 10,000 Daltons to 1,500,000 Daltons, 100,000 Daltons to 1,000,000 Daltons, and a solubility in tetrahydrofuran (THF) equal to or less than 1.0 microgram / mL at room temperature at 1 atmosphere, preferably a solubility in tetrahydrofuran (THF) equal to or less than 0.1 microgram / mL at room temperature at 1 atmosphere, more preferably a solubility in tetrahydrofuran (THF) equal to or less than 0.01 microgram / mL at room temperature at 1 atmosphere, and a sulfurized polymer represented by formula (V), wherein Q is a bonded sp2 carbon atom (C) or nitrogen (N), wherein Indicates a single bond or a double bond, S p represents a polysulfide and p ranges from 2 to 8, wherein the sulfurized polymer has a weight average MW of at least 2000, 10,000, 100,000 or 1,000,000 or a weight average MW ranging from 2000 Daltons to 2,000,000 Daltons, 10,000 Daltons to 1,500,000 Daltons, 100,000 Daltons to 1,000,000 Daltons,
[0276]
[0277] The weight ratio of the S-linked quinone copolymer represented by formula (II) to the sulfurized polymer represented by formula (V) ranges from 20:1 to 1:20, 10:1 to 1:10, 9:1 to 3:2, or 6:1 to 2:1, or is 1:1.
[0278] In some embodiments, the S-linked polymers, sulfurized carbon matrices, and / or composite materials described herein may be included in a redox-active composition that further comprises one or more additives described herein.
[0279] As used herein, "additive" means any component other than the redox-active polymer or the sulfided carbon matrix that enhances the mechanical, physical, electrical, or electrochemical properties of the electrode material. Exemplary additives include binders and conductive additives.
[0280] In some embodiments, the S-linked polymers, sulfurized carbon matrices, composites, and / or redox compositions described herein may be included in a cathode material, and in particular, in a cathode material configured to be in contact with a non-aqueous electrolyte of an electrochemical cell.
[0281] In the embodiments described herein, the S-linked polymers and / or composites of the present disclosure may be contained within an electrochemical cell.
[0282] As used herein, "electrochemical cell" refers to a device that is capable of generating electrical energy through a chemical reaction, or a device that is capable of utilizing electrical energy to drive a chemical reaction, or both.
[0283] An electrochemical cell that generates an electric current is called a voltaic cell or galvanic cell, and an electrochemical cell that generates a chemical reaction, for example via electrolysis, is called an electrolytic cell.
[0284] In particular, a voltaic cell (galvanic cell) is an electrochemical cell that generates electrical energy through a redox (reduction-oxidation) reaction in the cell. Electrochemical cells can also use externally applied electrical energy to drive the redox reaction within the cell, known as an electrolyzer. A fuel cell is an electrochemical cell that generates electrical energy from a fuel through an electrochemical reaction of hydrogen with an oxidant.
[0285] A voltaic cell or redox producing electrochemical cell may include a permeable barrier between two electrodes that allows anions and / or cations to pass from an electrolyte in contact with one electrode to an electrolyte in contact with the other electrode.
[0286] As used herein, "electrode" refers to a conductive material in contact with a non-conductive element. In the case of an electrochemical cell, the non-conductive element is an electrolyte in which a chemical reaction occurs. The two types of electrodes in a cell are an anode and a cathode. The anode is the electrode where electrons leave the electrochemical cell and oxidation occurs. The cathode is the electrode where electrons enter the cell and reduction occurs. By convention, when electrical energy is generated, the anode is considered to be the "negative electrode" and the cathode is considered to be the "positive electrode". When a cell uses electrical energy to drive a reaction (for example, when a rechargeable battery is being charged), the polarity of the cathode relative to the anode is negative, so the convention is usually (but not always) opposite. By changing the externally applied voltage between the electrodes (changing the direction of the current through the cell), the cell can be changed between generating energy (voltaic) and generating redox (electrolysis).
[0287] "Electric current" in the sense of this specification can be described as the flow of positive charge or the flow of an equal amount of negative charge in the opposite direction. By convention, regardless of the method of operation (voltaic vs. electrolytic), outside a single cell, current flows from cathode to anode (opposite to the direction of electron flow).
[0288] An electrochemical cell as described herein may include a cathode having a current collector on a metal substrate and an anode having a current collector on a metal substrate separated by a semi-permeable insulating membrane. The cell contains a non-aqueous salt solution that conducts ions. These components are placed in a container. Either the cathode or the anode may contain a redox active composition as described herein.
[0289] In particular, in some embodiments, an electrochemical cell is described that includes an anode, a cathode, and a non-aqueous electrolyte, wherein the anode electrode comprises a network polymer of formula (I) and / or a network dendrimer of formula (II) as described herein.
[0290] As used herein, "electrolyte" refers to a liquid or a mixture of a liquid and a solid containing at least cations and counterions for conducting ions during electrochemical reactions in an electrochemical cell. In some embodiments as described herein, the cations of the electrolyte may be lithium ions.
[0291] The electrolyte as described herein may have a mixture of cyclic carbonates of ethylene carbonate (EC) or monofluoroethylene carbonate (FEC) cosolvents, ethyl methyl carbonate (EMC), flame retardant additives, lithium salts, and electrolyte additives that improve compatibility and performance of lithium-ion batteries.
[0292] The lithium salt of the electrolyte as described herein may be selected from lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium bis(oxalato)borate (LiBOB), lithium hexafluoroarsenate (LiAsF 6 ), lithium perchlorate (LiClO 4 ), lithium trifluoromethanesulfonate (LiCF 3 SO 3 ), lithium bis(trifluoromethanesulfonyl)imide (LiN(SO 2 CF 3 ) 2 ), LiFSI and their mixtures.
[0293] The electrolyte additives described herein may include lithium bis(oxalate)borate (LiBOB), lithium difluoro(oxalate)borate (LiODFB), lithium tetrafluorooxalatephosphate (LiPF 4 (C 2 O4 )) and mixtures thereof.
[0294] The flame retardant additive of the electrolyte as described herein can be selected from triphenyl phosphate (TPhPh / TPP / TPPa), tributyl phosphate (TBP / TBuPh), triethyl phosphate (TEP / TEtPh), bis(2,2,2-trifluoroethyl)methylphosphonate (BTFEMP / TFMPo), tris(2,2,2-trifluoroethyl)phosphate, diethyl ethylphosphonate, diethyl phenylphosphonate, and mixtures thereof.
[0295] In some embodiments of the electrochemical cells of the present disclosure, the redox-active monomer portion comprises thiophene or anthraquinone, and the electrolyte is 1.0 M LiPF in EC:DEC (50:50 vol / vol). 6 EC and DEC refer to ethylene carbonate and diethyl carbonate, respectively.
[0296] In an alternative embodiment, for example, these electrochemical cells can feature a non-aqueous electrolyte at a concentration of 0.01M to 1M, including an organic solvent such as propylene carbonate, ethylene carbonate, dialkyl carbonate, DME, dioxolane, ether, fluorinated ether, glyme, acetonitrile, and one or more salts of lithium, sodium and / or potassium, such as lithium hexafluorophosphate (LiPF 6 ) lithium hexafluoroarsenate (LiAsF 6 ), lithium perchlorate (LiClO 4 ), lithium tetrafluoroborate (LiBF 4 ), lithium trifluoromethanesulfonate (LiCF 3 SO 3 ), lithium trifluoroacetate (LiCF 3 CO 2 ), lithium tetrachloroaluminate (LiAlCl 4 ), lithium bis(trifluoromethanesulfonyl)imide (Li[CF 3 SO 2 ] 2 N, LiTFSI), lithium bis(fluorosulfonyl)imide (Li[FSO 2 ] 2 N, LiFSI), lithium bis(oxalato)borate (Li[C 2 O 4 ] 2 B, LiBOB), lithium iodide (LiI), lithium bromide (LiBr), lithium chloride (LiCl) and lithium fluoride (LiF). In particular, the electrode as described in the present disclosure can be used as the cathode in such a non-aqueous single cell, and a low potential metal or alloy substance such as but not limited to lithium metal, lithiated graphite, lithium silicon alloy, magnesium or sodium or potassium as the anode.
[0297] In such non-aqueous cell embodiments as described above wherein Li metal is featured as the anode, the open circuit voltage of the cell (and therefore the cathode relative to Li + / Li relative potential) can be 2.0V to 3.5V.
[0298] A schematic diagram of a possible configuration of an electrochemical cell is shown in Fig.31 middle.
[0299] In particular, Fig.31 The figure above shows an exemplary electrochemical cell including an anode, a cathode, and an electrolyte disposed between the anode and cathode, and optionally a permeable barrier dividing the electrolyte into two ionically connected portions. Fig.31 The figure below shows an exemplary electrochemical cell in a pouch housing, comprising an anode, a cathode and their respective current collectors and an electrolyte disposed between the anode and cathode, and an optional separator that divides the electrolyte into two ionically connected portions. In some embodiments of the present disclosure, one or more electrochemical cells may be included in a battery.
[0300] As used herein, a "battery" is a device consisting of one or more electrochemical cells that generate electrical energy arranged in parallel (for increased capacity) or in series (for increased voltage). Battery types include redox-active polymer-metal, zinc-carbon, alkaline, nickel oxyhydroxide, lithium, mercuric oxide, zinc-air, Zamboni pile, silver-oxide, magnesium, nickel-cadmium, lead acid, nickel-metal hydride, nickel-zinc, silver-zinc, lithium-iron-phosphate, lithium ion, and others as will be appreciated by the skilled artisan.
[0301] In particular, a battery according to the present disclosure may include one or more electrochemical cells as described herein, and may further include a first electrode coupled to an anode of the one or more electrochemical cells, a second electrode coupled to a cathode of the one or more electrochemical cells, and a housing or casing encapsulating the one or more electrochemical cells.
[0302] In some embodiments, a battery in the sense of the present disclosure is composed of one or more electrochemical cells connected in parallel, in series, or in series and in parallel. In some embodiments, a battery may include a plurality of electrochemical cells that may be connected in series or in parallel based on performance requirements including voltage requirements, capacity requirements.
[0303] In some embodiments, electrochemical cells as described can be electrically connected in series to increase the voltage of the cell.
[0304] In some embodiments, electrochemical cells as described may be electrically connected in parallel to increase the charge capacity of the cell.
[0305] In some embodiments, the batteries as described herein can take the shape of a pouch, a prism, a cylinder, or a coin.
[0306] Fig.32 and Fig.33 A schematic diagram of the arrangement of electrochemical cells in a battery of the present disclosure is shown in FIG.
[0307] Fig.32 An exemplary arrangement of a plurality of electrochemical cells in a battery is shown. Fig.32 The figure above shows a plurality of electrically connected electrochemical cells electrically connected in parallel, and Fig.32 The following figure shows a plurality of electrically connected electrochemical cells electrically connected in series. The capacity of the battery of three cells connected in parallel is three times the capacity of a single cell. The voltage of the battery of three cells connected in series is three times the voltage of a single cell.
[0308] Fig.33 The figure above shows a plurality of electrically connected electrochemical cells electrically connected in parallel in an overlapping configuration, and Fig.33 The following figure shows a plurality of electrically connected electrochemical cells electrically connected in series.
[0309] The battery may be configured as a primary battery in which the electrochemical reaction between the anode and the cathode is substantially irreversible, or as a secondary battery in which the electrochemical reaction between the anode and the cathode is substantially reversible.
[0310] The batteries including S-linked quinone polymers, electrode materials, electrodes, and electrochemical cells of the present disclosure are long-life batteries. As used herein, the long life of a battery means that the battery can be charged / discharged for more than 1,000 cycles while maintaining 70% of the charge capacity. In some embodiments, the battery as described herein can have a life of at least four years. In some embodiments, the battery as described herein can be charged / discharged for more than 1,200 cycles while maintaining 70% of the charge capacity.
[0311] The S-linked polymers described herein, the sulfurized matrices described herein, and related composite electrode materials and / or electrodes to be included in electrochemical cells and batteries according to the present disclosure may be provided according to methods recognizable by a skilled artisan upon reading the present disclosure.
[0312] The S-linked polymers described herein for inclusion in electrochemical cells and batteries according to the present disclosure may be provided by methods recognizable to the skilled artisan upon reading the present disclosure.
[0313] In some embodiments, a method for preparing an S-linked quinone polymer is described. The method comprises:
[0314] Providing redox-active monomers Quinone monomers X 1 -MX 2 , where X 1 and X 2 represents the leaving group,
[0315] Provide a sulfide Sp source,
[0316] Make the redox active monomer quinone monomer X 1 -MX 2 contacting with a sulfide Sp source under suitable conditions and for a sufficient period of time to provide an S-linked quinone polymer represented by formula (I),
[0317] -[MS p ]- m
[0318] (Ij
[0319] in
[0320] M is a redox-active monomeric quinone moiety comprising a redox potential of 0.5 V to 3.5 V relative to the Li / Li+ electrode potential under standard conditions,
[0321] p refers to the number of sulfur atoms connected to the redox-active monomer quinone part M, and p ranges from 1 to 5. When p is 1, S p is a sulfide, or when p is 2 to 5, S p is a polysulfide, m ranges from 5 to 10,000,
[0322] wherein the S-linked quinone polymer has a weight average molecular weight of at least 1500 Daltons or a weight average MW ranging from 2000 Daltons to 2,000,000 Daltons, 10,000 Daltons to 1,500,000 Daltons, 100,000 Daltons to 1,000,000 Daltons, and a solubility in tetrahydrofuran (THF) equal to or less than 1.0 microgram / mL at 21°C at 1 atmosphere.
[0323] In some embodiments, leaving groups X1 and X2 can be independently selected from Cl-, Br-, I-, -OTs, -OMs, -OTf, or any other leaving group known to the skilled artisan.
[0324] In some embodiments, the sulfide Sp source includes but is not limited to elemental sulfur S8, Na 2 S.K. 2 S. Li 2S, any other sulfur-containing compound known to the skilled person.
[0325] In some embodiments, a method for preparing an S-linked quinone copolymer is described. The method comprises:
[0326] Providing redox-active monomers Quinone monomers X 1 -M1-X 2 and redox-active monomers quinone monomers X 1 -M2-X 2 , where X 1 and X 2 represents the leaving group,
[0327] Provide sulfide S p1 and S p2 The source,
[0328] Make the redox active monomer quinone monomer X 1 -M1-X 2 and redox-active monomers quinone monomers X 1 -M2-X 2 With sulfide S p1 and S p2 The source of is contacted under suitable conditions and for a sufficient period of time to provide an S-linked quinone polymer represented by formula (II)
[0329] -[M1-S p1 ] m1 -co-[M2-S p2 ]- m2
[0330] (II)
[0331] in
[0332] M1 and M2 are each a redox-active monomeric quinone moiety, which includes a redox potential of 0.5 V to 3.5 V relative to the Li / Li+ electrode potential under standard conditions, p1 and p2 each independently refer to the number of sulfur atoms connected to the redox-active monomeric quinone moiety M1 and the monomeric quinone moiety M2, respectively, and the range of p1 and p2 is each independently 1 to 5. When p1 is 1, S p1 is a sulfide, or when p1 is 2 to 5, S p1 For polysulfide, when p2 is 1, S p2 is a sulfide, or when p2 is 2 to 5, S p2 is a polysulfide, m1 and m2 are each independently in the range of 5 to 5,000, optionally the ratio of m1 to m2 is in the range of 1:50 to 1:1, 1:20 to 1:2, 1:6 to 1:3 or 1:5 to 1:4,
[0333] wherein the S-linked quinone polymer of formula (II) has a weight average molecular weight ranging from 1,000 Daltons to 2,000,000 Daltons or a weight average MW ranging from 2000 Daltons to 2,000,000 Daltons, 10,000 Daltons to 1,500,000 Daltons, 100,000 Daltons to 1,000,000 Daltons, and a solubility in tetrahydrofuran (THF) equal to or less than 1.0 micrograms / mL at 21°C at 1 atmosphere.
[0334] In some embodiments, leaving groups X1 and X2 can be independently selected from Cl-, Br-, I-, -OTs, -OMs, -OTf, or any other leaving group known to the skilled artisan.
[0335] In some embodiments, the sulfide S p1 and S p2 Sources include but are not limited to elemental sulfur S 8 、Na 2 S.K. 2 S. Li 2 S, any other sulfur-containing compound known to the skilled person.
[0336] As the skilled artisan will appreciate, specific chemical moieties, groups and substituents may be selected to provide the desired redox activity.
[0337] The term "chemical moiety" as used herein refers to an atom or group of atoms that, when included in a molecule, is responsible for the characteristic chemical reaction of the molecule, or an atom or group of atoms that remains after the reaction to become part of the reaction product. As will be understood by the skilled person, a chemical moiety comprising at least one carbon atom is also denoted an organic moiety.
[0338] In particular, as used herein, the term "organic moiety" refers to a carbon-containing portion of an organic molecule. For example, in an organic polymer, the organic moiety can be formed from different parts of the polymer, such as different parts of a monomer that remain in the polymer as part of a monomer unit of the polymer after polymerization. Exemplary organic moieties are provided by 1,5-dichloroanthraquinone or by an anthraquinone moiety that remains in an S-linked polymer as disclosed herein.
[0339] Exemplary chemical moieties within the context of the present disclosure are provided by functional groups such as hydrocarbon groups containing double or triple bonds, groups containing halogens, groups containing oxygen, groups containing nitrogen, and groups containing phosphorus and sulfur, all of which are identifiable by the skilled artisan.
[0340] The skilled artisan will be able to identify moieties that can be used in the methods of the present disclosure to provide the redox-active polycyclic compounds of the present disclosure.
[0341] S-linked polymers, sulfurized carbon matrices, redox compositions, redox composites, and related electrode materials, electrodes, and electrochemical cells can be included in systems in which polymers, matrix compositions, composite electrode materials, electrodes, and / or electrochemical cells are included in various combinations wherein they are interconnected in a configuration in which they function together as part of a mechanism and / or interconnected network according to the methods described herein.
[0342] In summary, electrode materials comprising S-linked polymers and sulfurized carbon matrices are described herein, as well as functional electrodes incorporating such materials and electrochemical cells and batteries comprising such electrodes. In certain embodiments, the electrode materials described herein exhibit high mechanical strength and excellent processability into functional electrodes due to their unique composition. Advantageously, in certain embodiments, due to the insoluble nature and stability of these organosulfur polymers in the non-aqueous electrolytes used, the electrodes support hundreds of cycles of battery charging and recharging without material loss.
[0343] In particular, S-linked quinone polymers, sulfurized carbon matrices and related compositions, composites, electrode materials, electrodes, electrochemical cells, and related methods and systems can be used in conjunction with applications in which the demand for high energy, high performance, safe, and long life batteries is rapidly increasing, for example due to environmental concerns.
[0344] S-linked quinone polymers, sulfurized carbon matrices and related compositions, composites, electrode materials, electrodes, electrochemical cells and related methods and systems can be used in conjunction with lithium-ion battery technology having various cathodes such as NMC, LFP, LMO, NCA that are currently widely used in electric vehicle applications.
[0345] In this regard, in some embodiments, the sulfided carbon matrix and related compositions, composite materials, electrode materials, electrodes, electrochemical cells, and related methods and systems can be used in conjunction with a Li anode in place of an inorganic cathode, which may be preferred, for example, given that the price of Li-ion battery technology has continued to decline over the past 30 years due to the adoption of improved processing and manufacturing practices. In particular, in those embodiments, the S-linked quinone polymers described herein, such as PAQT and 36PPAQS, 27PPAQS, are expected to improve the overall capacity and performance of composite cathodes of batteries and mixed mixtures of various ratios of PAQS, PAQT, 36PPAQS, 27PPAQS, PBQS, and various sulfided carbon matrix polymers (including but not limited to SPAN).
[0346] Additional details regarding organosulfur polymer and related composition electrochemical cells, battery methods and systems, including general fabrication and packaging of organosulfur polymer compositions, electrochemical cells and / or batteries can be determined by one of ordinary skill in the art upon reading this disclosure.
[0347] Example
[0348] The S-linked polymers, sulfurized carbon matrices, and related compositions, composites, electrode materials, electrodes, electrochemical cells, batteries, and related methods and systems described herein are further described in the following examples, which are provided by way of illustration and are not intended to be limiting.
[0349] In view of the content of this disclosure, the skilled person will be able to identify additional S-linked polymers, sulfurized carbon matrices and related compositions, compositions, electrode materials, electrodes, electrochemical cells, battery methods and systems. The following specific examples are given to illustrate the practice of the present invention, but should not be construed as limiting the present invention in any way.
[0350] In particular, exemplary redox-active S-linked polymers, sulfurized carbon matrices, composites, metals and related electrode materials, electrodes, devices, compositions, methods and systems are described in conjunction with specific experimental tests and procedures. A skilled artisan will be able to understand and determine the modifications required to apply the results illustrated in the exemplary embodiments of this section to additional embodiments of organosulfur polymers and related electrodes, devices, compositions, methods and systems according to the present disclosure.
[0351] As will be understood from the embodiments described herein, the features and properties of these organosulfur polymers described herein support their use as organic electrode materials suitable for a wide range of primary or rechargeable applications, such as batteries for electric vehicles, stationary batteries for emergency power supplies, local energy storage, starters or igniters, remote relay stations, communication base stations, uninterruptible power supplies (UPS), spinning reserve, peak load balancing, or other grid electricity storage or optimization applications. Small or micro battery applications are contemplated, including watch batteries, implanted medical device batteries, or sensing and monitoring system batteries (including gas or electricity metering), as are other portable applications such as flashlights, toys, power tools, portable radios and televisions, mobile phones, portable cameras, laptops, tablets or handheld computers, portable instruments, cordless devices, wireless peripherals, or emergency beacons. Military or extreme environment applications, including for satellites, munitions, robots, unmanned aerial vehicles, or for military emergency power or communications, are also possible.
[0352] Materials and methods
[0353] The following materials and methods can be used for all compounds listed herein and their precursors.
[0354] All electrochemical measurements of S-linked polymers, sulfided carbon matrices, and lithium systems were performed using a Biologic SP-150 potentiostat, a Neware tester, or an Arbin tester.
[0355] A beaker cell (or beaker cell as used interchangeably herein) was used for all cyclic voltammetry measurements of organosulfur polymers. The beaker cell comprises a glass container filled with electrolyte, a cathode organosulfur polymer material mixed with conductive carbon and additives as a working electrode (WE), and a Li / Li + As a reference electrode, and a Pt wire was used as a counter electrode (CE).
[0356] All polymers of the present disclosure were filtered and washed with deionized water and acetone until the solvent passing through the filter was clear.
[0357] To aid in cell formation and electrode conductivity, various additives are used, including but not limited to bismuth oxide, carbon black powder, graphite, carbon fiber, graphene, carbon nanofibers, and carbon fibers.
[0358] To enhance the adhesion, cohesion, and structural characteristics of the cathode or anode, carbon fibers, zirconium fibers, alumina fibers, or silica fibers have all been incorporated into the anode formulation.
[0359] In order to fix the cathode or anode to the substrate, a form of binder is used. Preferred binders may be PTFE, SBR, PVDF, HEC, CMC, gum arabic, xanthan gum, HPMC and chitosan.
[0360] The cathode or anode may be applied to the aforementioned substrate using a wet method by mixing all active materials and additives and a binder with water and then coating, or used as a dry powder and pressed onto the aforementioned substrate.
[0361] Example 1: Representative Vulcanized Carbon Matrix Polymer of PAQS-SPAN Composites
[0362] Sulfur-linked quinone polymers such as PAQS (poly[anthraquinone-sulfide]) have a theoretical capacity of 225 mAh / g, but in usable practical cells with lithium anodes, only deliver about 160 mAh / g at material loadings of >60% active cathode (required for cells with energy density for significant commercial applications), but have good cycling stability (>1000 cycles possible). + / Li, the discharge potential is typically about 2.5V to 2.0V.
[0363] In sulfurized carbon matrices such as SPAN (sulfurized poly[acrylonitrile]), it exhibits high capacity (3.0V to 0.50V, >200mAh / g) and better cycling stability than standard sulfur cathodes in electrochemical cells with lithium anodes; however, most of the capacity is obtained at lower potentials than conventional Li / S cells, and is therefore less preferred than Li / S compositions. The total S content in SPAN is about 25% to 50%, and its capacity can vary from 400 to 800mAh / g of total SPAN mass. As will be appreciated by the skilled artisan, sulfurized carbon matrix polymers generally have the same characteristics, with the S content being about 25% to 50% by weight relative to the total weight of the sulfurized carbon matrix polymer, and its capacity can vary from 400 to 800mAh / g of total polymer mass.
[0364] According to features of the present disclosure, the combination of organosulfur polymers and sulfurized polymer materials such as PAQS and SPAN in a mixed cathode material combination is expected to provide an active material that exhibits both the good cycling stability of the components PAQS and SPAN and the combined discharge capacity of the two materials. In particular, for example, relative to Li + / Li, the mixture can provide a capacity of >250 mAh / g from 3.2 V to 1.0 V and a cycling stability of >100 cycles.
[0365] In particular, exemplary organosulfur polymers known or contemplated for inclusion in the composite materials of the present disclosure include those capable of reacting with respect to Li + / Li redox-active polymers that undergo a reversible redox process at a high potential of 100 mAh / g, thereby increasing the overall energy density of the battery. Exemplary polymers with the above characteristics include S-linked quinone polymers, including 36PPAQS, 27PPAQS, and PAQT. The capacity of both 36PPAQS and 27PPAQS is 225 mAh / g, however, when combined with metallic lithium as an anode in a non-aqueous electrolyte, they produce a 2.8 V battery compared to PAQS at 2.2 V. PAQT is a new polymer with a theoretical capacity of 400 mAh / g, and relative to Li / Li + The redox potential of is 2.8 V. In general, Figure 1 As shown in the table, the energy density of these new polymers is higher than that of the PAQS alone.
[0366] Additional exemplary organosulfur polymers that can be used in the composite materials of the present disclosure include S-linked copolymers of two quinone moieties as cathode active materials for non-aqueous rechargeable batteries. PAQS is selected as the major component of the copolymer, and poly-1,4-benzoquinone sulfide (PBQS) is selected as the minor component of the copolymer. Additional exemplary organosulfur polymers include S-linked copolymers configured to increase the capacity of PAQS by 20%, such as PAQS 0.8 BQ 0.2 .
[0367] Mixed mixtures of S-linked quinone polymers (including PAQS) and sulfurized carbon matrices (such as, but not limited to, sulfurized polyacrylonitrile (SPAN)) are also contemplated in the present disclosure. Although non-aqueous batteries using PAQS as cathode active materials show excellent cyclability, the energy density is limited due to the two carbonyl redox active centers, which only yield a theoretical capacity of 225 mAh / g. In the present disclosure, we contemplate adding high capacity sulfur-containing polymers to PAQS to make mixed mixtures of cathode materials that provide higher overall capacity and, therefore, higher energy density batteries. In some embodiments, by combining 10 wt % to 60 wt % of a sulfurized carbon matrix, such as a SPAN polymer, with an organic sulfur polymer, such as a PAQS material, the energy density can be increased by 20% to 60%. In some embodiments, by combining 10 wt % to 90 wt % of SPAN or other sulfurized carbon matrix polymers with an organic sulfur-S-polymer, such as a PAQS material, the energy density can be increased by 20% to 250%.
[0368] In particular, the S-linked quinone polymers described in the present disclosure include S-linked condensation polymers based on anthraquinone (AQ), phenanthrenequinone (PAQ), anthraceneteterone (AQT), and 1,4-benzoquinone (BQ), and are catalytically active under standard conditions relative to Li / Li + The electrode potential has a redox potential range of 1.0V to 3.5V. Figure 2 Exemplary structures of S-linked quinone polymers are shown.
[0369] In addition, copolymers of sulfur-linked quinone polymers are useful and can be formed by condensing suitable monomers with sulfur materials under typical conditions described below. For example, copolymers of PAQS or PAQT and PBQS can be formed. PAQS is a robust polymer that provides 1000 cycles at >80% active material, but only provides a capacity of 160 mAh / g at low rates. This can be improved in a range of PAQS-PBQS or copolymers (e.g., random copolymers) by varying the ratio of the monomers. By incorporating up to 20 mol % PBQS in the copolymer, we obtained a 20% capacity improvement from PAQS ( Figure 3 ). Similar results can be obtained using PAQT monomer and PBQS.
[0370] Figure 3 Shown are the structures of PAQS or copolymers of PAQT and PBQS encompassed in the present disclosure.
[0371] In particular, embodiments of the present disclosure generally utilize high sulfur content polymers or sulfurized carbon matrices (e.g. Figure 4 The sulfurized carbon substrates described in this disclosure are n-type and have a redox potential of 1.1 % relative to Li / Li under standard conditions. + The electrode potential has a redox potential range of 1.0V to 2.5V or 11.0V to 3.5V.
[0372] Figure 4 The structure of a sulfurized carbon matrix used as one of the components in an -S- linked organic quinone polymer is shown. The properties of the sulfurized carbon matrix of the present disclosure will be described below with reference to a representative sulfurized polyacrylonitrile (SPAN). The relevant features are applicable to other sulfurized carbon matrices, as will be understood by the skilled person when reading the present disclosure.
[0373] Sulfurized polyacrylonitrile (SPAN) is one such material first reported by Wang et al. in 2002. [6][7][8][9]
[10] SPAN is chemically and electrochemically different from elemental sulfur and any composite cathode based on elemental sulfur. Elemental sulfur is an insulating material with an eight-membered ring structure, while SPAN is a conductive material in which active sulfur is chemically embedded in a conductive matrix of carbonized PAN polymer, such as Fig.30 as shown in .
[0374] Fig.30 Shown is a structural comparison of elemental S and sulfurized polyacrylonitrile (SPAN).
[0375] During discharge, elemental sulfur or sulfur composites with elemental sulfur react with the electrolyte by converting cyclic S 8 The ring opens to form long-chain linear lithium polysulfides, while in SPAN, the active sulfur moiety is covalently linked to the carbon framework, so no such long-chain linear lithium polysulfides are formed. Since there is no long-chain linear polysulfide formation in the case of SPAN, there is no lithium polysulfide dissolution, and therefore no shuttling mechanism.
[0376] Furthermore, the sulfur content in elemental sulfur is 100%, while the sulfur content in SPAN varies between 30% and 60% depending on the synthesis. The higher the synthesis temperature, the lower the sulfur content in the polymer matrix. The synthesis process of SPAN used in the present disclosure is described in Example 37. Based on TGA and elemental analysis, the sulfur content was found to be 40%.
[0377] Many examples of improved SPAN and SPAN-like materials are known in the literature and are summarized in Figure 4 middle.
[0378] Both S and SC cathodes form soluble long-chain polysulfides during discharge. The lithium salts of these polysulfides are nucleophilic in nature and are able to react with any electron-deficient species. In the presence of quinone polymers as co-active materials in the hybrid cathode, the soluble polysulfides can react with the carbonyl groups of the polymers and destroy them for intercalation into Li during cycling. + and + However, as used herein, in the case of SPAN, SC means carbon, and S can be written as SC. CS refers to a premix of electrocarbon and sulfur, optionally containing additives. Since no soluble polysulfides are formed, no such harmful reactions occur during cycling.
[0379] Elemental sulfur is an insulating material. Conductive carbon and additives can be added to elemental sulfur for electron conduction during battery cycling. In addition, elemental sulfur forms polysulfides during discharge that are soluble in organic electrolytes. The solubility of polysulfide discharge products in electrolytes leads to a shuttle effect, which is detrimental to battery performance. To address these two issues, elemental sulfur (S 8 Sulfurized polyacrylonitrile (SPAN) was synthesized by heat treatment of polyacrylonitrile (PAN) and polyacrylonitrile (PAN) at different temperatures. [6] Elemental sulfur was embedded into the backbone of the pyrolyzed PAN polymer as C-S bonds in SPAN as confirmed by FTIR, Raman spectroscopy, and XPS.
[11] The conjugated nature of SPAN improves the conductivity of the material, and the C-S bonds throughout the structure prevent the formation of soluble polysulfides. The amount of sulfur in SPAN is about 25 wt% to 60 wt%.
[0380] Described are exemplary polymers of random copolymers including PAQT, 36PPAQS, and PAQS-PBQS. PAQT has a higher voltage and capacity than PAQS. PAQT has a redox voltage of 2.80V and a capacity of 400mAh / g, compared to the redox voltage and capacity of PAQS of 2.20V and 225mAh / g, respectively. Similarly, 36PPAQS has an improved redox voltage of 2.70V and a capacity of 225mAh / g, respectively.
[0381] In the experimental data presented here, we found that SPAN acts as a co-active material with PAQS. Both SPAN and PAQS have their characteristic voltage curves in the discharge-charge curve. However, S or SC do not act as co-active materials in the same electrolyte, and when the battery is assembled and cycled under the same conditions, the characteristic voltage curve of PAQS is not obvious during the discharge-charge curve.
[0382] Example 2: Anode
[0383] The anode active materials of the present disclosure include, but are not limited to, metallic lithium in the form of lithium foil, powdered lithium, lithium deposited on a conductive or non-conductive substrate such as copper foil, lithium alloys such as lithium aluminum alloys, lithium tin alloys. In some embodiments, the anode active material can be metallic sodium, metallic potassium, graphite, hard carbon, silicon-based materials. In some embodiments, the anode can be coated with carbon, graphite, non-redox active polymers to prevent the formation of dendrites during cycling.
[0384] Example 3: Cathode
[0385] The cathode electrode composition comprises a PAQS:SPAN active material, one or more conductive carbons, and one or more binder materials. The PAQS and SPAN or other vulcanized polymer composition can vary from 90 wt% PAQS to 20 wt% or less to 5 wt% PAQS, and the remaining amount of each cathode can be from 5 wt% to 10 wt% to 80 wt% SPAN material or any other vulcanized polymer material. In some embodiments, 36PPAQS, PAQT, modified PAQS can be used as cathode active materials separately, or in combinations of various ratios from 20 mol% to 80 mol% thereof as cathode active materials. In some embodiments, various combinations of 36PPAQS:SPAN, PAQT:SPAN, BQ:SPAN, PAQS in a ratio of 90 wt% to 20 wt% or as low as 5 wt% 0.8 -BQ 0.2 The mixed mixture of :SPAN can be used as a cathode active material. In some embodiments, an electrode composition comprising an n-type redox polymer, a sulfurized carbon matrix polymer, a binder and a conductive additive can be used.
[0386] Example 4: Binder
[0387] The binder may be 0.5 wt % to 15 wt % of one or more selected from the group consisting of polytetrafluoroethylene (PTFE), styrene-butadiene or styrene butadiene rubber (SBR), poly(vinylidene fluoride) (PVDF), poly(tetrafluoroethylene), sodium or lithium carboxymethyl cellulose (CMC), styrene butadiene rubber, polyacrylic acid (PAA), polyvinyl alcohol (PVA), polyethylene glycol or polyethylene oxide (PEG or PEO), polyamideimide (PAI), polyacrylonitrile (PAN) xanthan gum, gum arabic and agar, any combination thereof. In some embodiments, the electrode composition comprising a redox polymer and a sulfurized carbon matrix polymer may be present at 20% to 80% or 20% to 95% by weight of the total electrode composition. As the conductivity of the active material or network polymer increases, the amount of the conductive additive in the electrode may be appropriately reduced while maintaining the same degree of conductivity of the electrode composition. As the stability of the active material or network polymer increases, the amount of binder in the electrode can correspondingly reduce the physical stability of the electrode composition.In some embodiments, an electrode composition comprising an n-type redox polymer, a sulfided carbon matrix polymer, and a binder can be used.
[0388] Example 5: Conductive Additives
[0389] The conductive additive may be 5 wt % to 25 wt % of one selected from the following group: carbon black (acetylene black, Super P Li, C-energy, Ketjen Black-300, Ketjen Black-600), Imerys (Super P, Super PC65, C-Nnergy), carbon nanotubes (Cnano, Tuball), graphene (xGnP R grade, xGnP H grade, xGnP C grade, xGnP M grade) and graphite (KS-4, KS-8, KC-4, KC-8) and nickel powder, or any combination thereof. As used herein, a binder as used herein refers to a polymer material that is not redox active but enhances the adhesion of an electrode under battery operating conditions.
[0390] Example 6: Mixing process
[0391] In the embodiments described herein, the n-type polymers and the sulfurized carbon matrix polymers of the present disclosure can be incorporated into the functional electrodes by mixing with suitable binders and conductive additives. Mixing methods include planetary mixing and high shear mixing. Electrode coating methods include drop casting, blade coating, spin coating, comma roller coating and extrusion. In some embodiments, the composition of the electrode can vary from 30% to 100% by weight of active materials, 5% to 70% by weight of conductive additives and 1% to 20% by weight of binders, and the total weight % of all substances is 100%. After such electrodes are mixed, coated and dried, the electrodes are subjected to pressure by calendering and then heated at a temperature above 50°C. Calendering can be achieved using heated or unheated rollers.
[0392] Example 7: Separator
[0393] The electrochemical cell described in the present invention includes an anode, a cathode, an electrolyte and a separator. The separator is arranged between the cathode and the anode, and can be any porous non-conductive polymer material, which is non-reactive and can isolate the anode active material and the cathode active material, but can conduct ions between them. Typical examples of separators include, but are not limited to, polyolefins, such as polyethylene and polypropylene, glass fiber paper and ceramic materials. In some embodiments, Celgard 2400 is used as a separator. In some embodiments, Celgard 3501 is used as a separator. In some embodiments, Celgard 2325 is used as a separator. In other embodiments, polypropylene SH2214 is used as a separator. Separators of different thicknesses ranging from 5 microns to 50 microns are used in the present invention.
[0394] Example 8: Electrolyte:
[0395] The non-aqueous electrolyte used in the present invention includes, but is not limited to, non-cyclic ethers, cyclic ethers, glycol dimethyl ethers, polyethers, cyclopentanes, sulfones, acetals, ketals, carbonates, dioxolanes, and mixtures thereof. Examples of non-cyclic ethers include, but are not limited to, 1,2-dimethoxyethane (DME), trimethoxyethane (TME), diethyl ether (DEE), partially fluorinated ethers such as bis(trifluoroethyl) ether (BTFE), perfluorinated ethers, dimethoxypropane, diethoxyethane. Examples of cyclic ethers include, but are not limited to, 1,4 ... Alkane, 1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran. Examples of polyethers include, but are not limited to, diethylene glycol dimethyl ether (diglyme), triethylene glycol dimethyl ether (triglyme), tetraethylene glycol dimethyl ether (tetraglyme), higher molecular weight glycol dimethyl ether, diethylene glycol divinyl ether, ethylene glycol divinyl ether, triethylene glycol divinyl ether, tetraethylene glycol divinyl ether. Examples of sulfones and sulfolanes include, but are not limited to, 3-methyl sulfolane, 3-sulfolane, dimethyl sulfone, diethyl sulfone, sulfolane, 3-fluorosulfolane. Examples of carbonate solvents include, but are not limited to, dimethyl carbonate (DMC), diethyl carbonate (DEC), propylene carbonate (PC), ethylene carbonate (EC), vinylene carbonate (VC).
[0396] Examples of lithium salts used in the present disclosure include, but are not limited to, LiTFSI, LiOTf, LiClO 4 , LiBF 4 、LiPF 6 、LiSCN、LiI、LiAsF 6 、LiFSI、LiNO 3 , LiF, LiOAc, lithium formate, LiSO 3 CH 3 The concentration of lithium salt used ranged from 0.5M to 6M.
[0397] Example 9: S-Linked Polymer (PAQS) Cathode
[0398] The cathode consisted of PAQS active material, conductive carbon and PVDF binder in different ratios. A typical cathode consisted of 70 wt% PAQS, 20 wt% SP carbon and 10 wt% PVDF. First, the PAQS and SP powders were mixed in a coffee mixer. Then a calculated amount of a 3 wt% solution of PVDF in NMP was added to the PAQS:SP mixture in a screw-top cup. The entire mixture was then placed in a Thinky centrifugal mixer and mixed at 2000 rpm for 30 seconds for a total of 3 times. The honey-like material was coated onto a carbon-coated aluminum foil using an automatic coater. The coated material was then dried under vacuum at 100°C overnight. The typical thickness of the electrode is about 40 microns to 100 microns, and the typical loading range of the active material is 3 mg / cm 2 Up to 10mg / cm 2 .
[0399] Example 10: 36PPAQS cathode
[0400] The 36PPAQS cathode was prepared by mixing 36PPAQS, SP, KB (Ketjen black) in a mortar using a pestle. A 3 wt% solution of PVDF in NMP was added to the mixed powder in a plastic cup that could be sealed with a screw cap. The entire mixture was then placed in a Thinky centrifugal mixer and spun at 2000 rpm for 30 seconds, 3 times. The concentrated solution was coated onto a carbon-coated aluminum foil using an automatic coater. The coated foil was then dried overnight at 120°C under vacuum. The final composition of the electrode was 36PPAQS:SP:KB:PVDF (70:18:2:10).
[0401] Example 11: 27PPAQS cathode
[0402] The 27PPAQS cathode was prepared by mixing 27PPAQS and SP in a mortar using a pestle. A 3 wt% solution of PVDF in NMP was added to the mixed powder in a plastic cup that could be sealed with a screw cap. The entire mixture was then placed in a Thinky centrifugal mixer and spun at 2000 rpm for 30 seconds, 3 times. The concentrated solution was coated onto a carbon-coated aluminum foil using an automatic coater. The coated foil was then dried overnight at 120°C under vacuum. The final composition of the electrode was 27PPAQS:SP:PVDF (70:20:10).
[0403] Example 12: PAQT cathode
[0404] First, PAQT, SP, and PTFE were mixed in H 2 A typical PAQT cathode was prepared in NMP (50:50) of 1% NMP: EtOH (50:50). The solvent was dried at 80°C overnight. The PAQT: SP: PTFE mixture was then densified and granulated. A 3 wt% solution of PVDF in NMP was added to the densified and granulated mixture in a plastic cup that could be sealed with a screw cap. The entire mixture was then placed in a Thinky centrifugal mixer and spun at 2000 rpm for 30 seconds, 3 times. The concentrated solution was applied to a carbon-coated aluminum foil using an automatic coater. The coated foil was then dried under vacuum at 120°C overnight. The final composition of the electrode was PAQT: SP: PTFE: PVDF (70:20:2:8).
[0405] Example 13: PAQS:SPAN cathode
[0406] Composite hybrid cathodes of various ratios of S-linked quinone polymers and sulfided carbon matrix polymers were prepared. The amount of S-linked quinone polymer PAQS varied between 5 wt% and 80 wt% or 60 wt% and 80 wt% relative to the total weight of the S-linked quinone polymer and the sulfided carbon matrix polymer, and the remaining active material was SPAN. A typical procedure for making a PAQS:SPAN hybrid cathode is as follows. First, a specific ratio of SPAN:SP mixture was ball milled for 10 minutes. The SPAN:SP mixture was then added to the PAQS and mixed thoroughly using a coffee mixer. A calculated amount of a 3 wt% solution of PVDF in NMP was added to the powder mixture of PAQS:SPAN:SP in a cup sealed with a screw cap. The entire mixture was then placed in a Thinky centrifugal mixer and then mixed at 2000 rpm for 30 seconds for at least 3 times. The viscous honey-like material was coated on a carbon-coated aluminum foil. The NMP was dried at 80°C.
[0407] The following PAQS:SPAN cathode was prepared by following the above steps:
[0408] (1)PAQS:SPAN:SP:PVDF (45:22:23:10% by weight)
[0409] (2)PAQS:SPAN:SP:PVDF (50:30:10:10% by weight)
[0410] (3)PAQS:SPAN:SP:PVDF (75:15:5:5% by weight)
[0411] (4)PAQS:SPAN:SP:PVDF (75:17:5:3% by weight)
[0412] (5)PAQS:SPAN:SP:PVDF (70:20:5:5% by weight)
[0413] (6)PAQS:SPAN:SP:PVDF (65:25:5:5% by weight)
[0414] (7) PAQS:SPAN:SP:PVDF (60:30:5:5% by weight).
[0415] Example 14: PAQS 0.8 BQ 0.2 Electrode preparation
[0416] Use a mortar and pestle to grind PAQS 0.8 BQ 0.2The copolymer was mixed with Super P (SP) carbon. A 3 wt% solution was added to the mixture. A 3 wt% solution of PVDF in NMP was added to the mixed powder in a plastic cup that could be sealed with a screw cap. The entire mixture was then placed in a Thinky centrifugal mixer and spun at 2000 rpm for 30 seconds for a total of 3 times. The concentrated solution was coated onto a carbon-coated aluminum foil using an automatic coater. The coated foil was then dried overnight at 100°C under vacuum. The final composition of the electrode was PAQS 0.8 BQ 0.2 :SP:PVDF (70:20:10 wt %).
[0417] Example 15: Electrolyte Preparation
[0418] All electrolytes are in H 2 O and O 2 Levels <10 ppm were prepared in a glove box by mixing the appropriate lithium salt and solvent as described in the table below. 2 The O content was measured by Karl Fischer titration. It was found that H 2 O levels <25ppm.
[0419]
[0420]
[0421] Example 16: Coin cell preparation:
[0422] Place all 2032 coin cells in H 2 O and O 2 Assembled in glove box with level <10ppm. Lithium foil (0.02mm thick, MTI) was used as anode. Celgard 2400 and 2325 polypropylene membranes were used as separators. Typical thickness range of electrodes was 50mm to 100mm. Typical mass loading range was 3mg / cm 2 Up to 10mg / cm 2 The typical loading range of electrolyte is 50mL to 100mL.
[0423] Example 17: Li / / 36PPAQS coin cell
[0424] In this example, 36PPAQS polymer (also referred to herein as Gen 2) was used as the cathode active material. The cathode was prepared by mixing 1.35 g of 36PPAQS polymer: SP: KB (70: 18: 2 weight ratio) in a mortar using a pestle. A 3 wt % solution of PVDF in NMP (5.0 g) was added to the mixed powder in a plastic cup. An additional 2.0 g of NMP was added to improve the texture and viscosity of the slurry. The entire mixture was then placed in a Thinky centrifugal mixer and centrifuged at 2000 rpm for 30 seconds for a total of 3 times. A uniform viscous solution was applied to a carbon-coated aluminum foil using an automatic coater. The coated foil was then dried overnight at 120 ° C under vacuum and stored in an argon glove box. The final composition of the electrode is shown as 36PPAQS: SP: KB: PVDF (70: 18: 2: 10 weight ratio).
[0425] Use lithium chip (0.02mm, 1.54cm 2 ) as the anode and using the above 36PPAQS:SP:SP:KB:PVDF (2.9 mg, 1.13 cm 2 ) as the cathode of the double-electrode CR2032 coin-type single cell. The diameter of the cell was 18 mm (2.54 cm 2 ) as separator. Various electrolyte formulations were tested, but in this example, 50 μL of 2M LiTFSI in DME:13DOL (1:1 volume) electrolyte formulation (ANA-6) was used. The single cell was cycled at C / 10 rate with voltage cutoffs of 1.6 V to 3.6 V. The charge and discharge characteristics of the single cell at C / 10 are shown in Figure 5 When combined with a metallic lithium anode, the polymer produced a 2.70V battery with a weight average MW ranging from 1,000Da to 2,000,000Da.
[0426]
[0427] The cycling performance of the single cell assembled in ANA-6 is shown in Figure 6 A low specific capacity (about 50 mAh / g) was obtained in the initial cycles, which increased with cycling, reaching a maximum capacity of 152 mAh / g, which is about 68% of the theoretical capacity of the polymer. No significant capacity decay was observed until 60 cycles, and then slight capacity decay was observed until 100 cycles. Coulombic efficiencies >99.5% ( Figure 7 ).
[0428] Example 18: Li / / PAQT coin cell
[0429] In this example, an S-linked PAQT polymer, designated Gen3, was used as the cathode active material with a weight average MW range of 1,000 Da to 2,000,000 Da. The synthesis of this S-linked quinone polymer is presented in Scheme 4. The PAQT (0.52 g) polymer, SP carbon (0.15 g) and 60% PTFE (0.015 g) aqueous suspension were mixed in 1.5 mL of EtOH:H 2 The cathode was prepared by mixing EtOH:H O (1:1). The mixture was mixed at 2000 rpm for 30 seconds using a Thinky centrifugal mixer. 2 The solvent mixture was dried at 80°C overnight, and the remaining powder was then densified and granulated into a fine powder. A 3 wt% solution of PVDF in NMP (2.0 g) was added to the granulated powder (0.72 g) in a plastic cup. The entire mixture was then placed in a Thinky centrifugal mixer and centrifuged at 2000 rpm for 30 seconds for a total of 3 times. In order to obtain the appropriate slurry viscosity and texture, an additional amount of pure NMP was added to the mixture, which was then subsequently centrifuged at 2000 rpm for 30 seconds. A total of 3.0 g of NMP was added to the mixture. The uniform viscous slurry was applied to a carbon-coated aluminum foil using an automatic coating machine. The coated foil was then dried overnight at 120°C under vacuum and stored therein for 4 hours. 2 O and O 2 The final composition of the electrode was shown to be PAQT:SP:PTFE:PVDF (70:20:2:8 weight ratio).
[0430]
[0431] Use lithium chips (thickness 0.02mm, 1.54cm 2 ) as the anode and using the above PAQT:SP:PTFE:PVDF (4.57 mg, 1.13 cm 2 ) as the cathode of the double-electrode CR2032 coin-type single cell. The diameter of the cell was 18 mm (2.54 cm 2 ) as the separator. Various electrolyte formulations were tested, but in this example, 60 μL of 2M LiTFSI in DME:13DOL (1:1 volume) + 100 mM LiNO 3 The electrolyte formulation (ANA-7) in gives the best cycling data. The charge and discharge characteristics of the single cell at C / 10 are presented in Figure 8 When combined with a metallic lithium anode, this PAQT polymer produced a 2.80V battery.
[0432] Figure 8 The voltage curves (charge and discharge characteristics) of a Li / / PAQT single cell in ANA-7 at C / 10 are shown.
[0433] The galvanostatic cycling curves of Li / / PAQT cells in ANA-7 electrolyte at C / 10 are shown in Fig. 9 PAQT is a sulfide polymer with four carbonyl groups in its structure, which is able to exchange 4 electrons during cycling, which corresponds to a theoretical specific capacity of 400 mAh / g. In our experiments, Li / / PAQT 2032 coin cells exhibited a capacity of 162 mAh / g at C / 10, as shown in Figure 2. Figure 8 As shown. A low specific capacity (about 50 mAh / g) was obtained in the initial cycles, indicating that the electrode reorganization and wetting occurred, which may be related to the high viscosity of the applied electrolyte. The specific capacity increased with cycling, reaching a maximum capacity of 162 mAh / g after 50 cycles, which is about 40% of the theoretical capacity of the polymer. No capacity decay was observed until 124 cycles. For single cells up to 124 cycles, Coulombic efficiencies >99.8% ( Fig.10 ).
[0434] Li / / PAQS:SPAN coin cell example
[0435] Example 19: Li / / PAQS:SPAN:SP:PVDF (45:22:23:10) coin cell
[0436] In this example, a mixed mixture of PAQS and a sulfurized organosulfur polymer (SPAN) was used as the cathode active material. The cathode was prepared by first ball milling a 1:1 mixture of SPAN and SP for 30 minutes using a high-energy ball mill. Then 0.22 g of the SPAN:SP (1:1) mixture was placed in a mortar, to which PAQS (0.24 g) was added, and a pestle was used to mix them thoroughly. The entire mixture was placed in a plastic cup, and a 3 wt % solution of PVDF in NMP (1.70 g) was added. The sealed cup with the mixture was then placed in a Thinky centrifugal mixer and centrifuged at 2000 rpm for 30 seconds for a total of 3 times. A viscous slurry of uniform appearance was obtained, which was coated onto a carbon-coated aluminum foil using an automatic coating machine. The coated foil was then dried overnight at 80 ° C under vacuum and stored in H 2 O and O 2 The final composition of the electrode was shown to be PAQS:SPAN:SP:PVDF (45:22:23:10 weight ratio).
[0437] Fig.11The voltage curves (charge and discharge characteristics) of a Li / / PAQS:SPAN single cell in ANA-4 at C / 10 are shown.
[0438] Use lithium chips (thickness 0.02mm, 1.54cm 2 ) as the anode and using the above PAQS:SPAN:SP:PVDF (2.90 mg, 1.13 cm 2 Electrochemical tests were performed using a two-electrode CR2032 coin-type cell with a cathode. 2 ) as the separator. Various electrolyte formulations were tested, but in this example, it was found that the electrolyte formulation (ANA-4) of 80 μL of 1M LiTFSI in DME:13DOL (1:1 volume) gave the best cycling data ( Fig.11 The single cell was cycled at C / 10 with a voltage cutoff of 3.1 V to 1.1 V. When combined with a metallic lithium anode, this PAQS:SPAN polymer hybrid blend produced an average 2.0 V battery ( Fig.11 The total discharge capacity of the single cell was found to be 285 mAh / g, which is >75% higher than that of the cathode using PAQS polymer alone.
[0439] Fig.12 The discharge capacity vs. cycle number of the Li / / PAQS:SPAN cell in ANA-4 at C / 10 is shown. Fig.12 The data show remarkable stability of discharge capacity up to 82 cycles. Coulombic efficiency vs. cycle number is presented in Fig.13 , which showed excellent Coulombic efficiency up to 81 cycles. Fig.13 Shown is the Coulombic efficiency vs. cycle number of Li / / PAQS:SPAN single cells in ANA-4 at C / 10.
[0440] The total energy density of the system (kWh / kg) vs. the number of cycles is presented in Fig.14 The total energy density was found to be >550Wh / kg and was remarkably stable up to at least 82 cycles.
[0441] Fig.14 Shown is the energy density (kWh / g) vs. cycle number of Li / / PAQS:SPAN cells in ANA-4 at C / 10.
[0442] Example 20: PAQS:SPAN:SP:PTFE:PVDF (48:38:10:1:4)
[0443] In this example, a PAQS:SPAN polymer blend was used as the cathode active material. 0.34 g PAQS polymer, 0.27 g SPAN and SP carbon + PTFE (0.07 g) were first mixed in 1.0 mL EtOH:H 2 The cathode was prepared by mixing EtOH:H O (1:1). The mixture was mixed by Thinky centrifugal mixer at 2000 rpm for 30 seconds. 2 The solvent mixture was dried at 80°C overnight, and the remaining powder was then densified and granulated into a fine powder. A 3 wt% solution of PVDF in NMP (0.9 g) was added to the granulated powder (0.72 g) in a plastic cup. The entire mixture was then placed in a Thinky centrifugal mixer and centrifuged at 2000 rpm for 30 seconds for a total of 3 times. In order to obtain the appropriate slurry viscosity and texture, an additional amount of pure NMP was added to the mixture, which was then subsequently centrifuged at 2000 rpm for 30 seconds. A total of 0.2 g of NMP was added to the mixture. The uniform viscous slurry was applied to a carbon-coated aluminum foil using an automatic coating machine. The coated foil was then dried overnight at 100°C under vacuum and stored therein for 4 hours. 2 O and O 2 The final composition of the electrode was shown to be PAQS:SPAN:SP:PTFE:PVDF (48:38:9:1:4 weight ratio).
[0444] Fig.15 The voltage curves (charge and discharge characteristics) of a Li / / PAQS:SPAN (48:38) single cell in ANA-6 at C / 10 are shown.
[0445] Use lithium chips (thickness 0.02mm, 1.54cm 2 ) as the anode and using the above PAQS:SPAN:SP:PTFE:PVDF (3.23 mg, 1.13 cm 2 Electrochemical tests were performed using a two-electrode CR2032 coin-type cell with a cathode. 2 ) as the separator. Various electrolyte formulations were tested, but in this example, it was found that 80 μL of 2M LiTFSI in DME:13DOL (1:1 volume) electrolyte formulation (ANA-6) gave the best cycling data ( Fig.16 ). The cell was cycled at C / 10 with a voltage cutoff of 3.1 V to 1.1 V. The charge and discharge characteristics of the cell at C / 10 are shown in Fig.15The total discharge capacity of the single cell was found to be 235 mAh / g, which is >47% higher than the cathode with PAQS polymer alone. The discharge capacity is slightly lower than the single cell described in the previous example, which may be due to the addition of 1% PTFE in the cathode.
[0446] Fig.16 The discharge capacity vs. cycle number of Li / / PAQS:SPAN (48:38) cells in ANA-6 at C / 10 is shown. Fig.16 The data show remarkable stability of discharge capacity up to 18 cycles. Coulombic efficiency vs. cycle number is presented in Fig.17 , which shows 100% Coulombic efficiency up to 18 cycles. Fig.17 Shown is the coulombic efficiency vs. cycle number of Li / / PAQS:SPAN (48:38) single cells in ANA-6 at C / 10.
[0447] Example 21: PAQS:SPAN:SP:PVDF (70:20:5:5)
[0448] In this example, a mixed mixture of PAQS and sulfurized polyacrylonitrile polymer (SPAN) was used as the cathode active material. The cathode was first prepared by mixing PAQS (0.70 g), SPAN (0.20 g) and SP (0.05 g) together in a mortar and pestle. The entire mixture was placed in a plastic cup and a 3 wt % solution of PVDF in NMP (1.70 g) was added. The cup with the mixture was then placed in a Thinky centrifugal mixer and centrifuged at 2000 rpm for 30 seconds for a total of 3 times. In order to obtain the appropriate slurry viscosity and texture, additional amounts of pure NMP were sequentially added to the mixture, followed by subsequent centrifugation at 2000 rpm for 30 seconds. A total of 0.5 g of pure NMP was added to the mixture. A viscous slurry of uniform appearance was obtained, which was then coated onto a carbon-coated aluminum foil using an automatic coating machine. The coated foil was then dried overnight at 80° C. under vacuum and stored therein for 3 hours. 2 O and O 2 The final composition of the electrode was shown to be PAQS:SPAN:SP:PVDF (70:20:5:5 weight ratio).
[0449] Fig.18 The voltage curves (charge and discharge characteristics) of a Li / / PAQS:SPAN (70:20) single cell in ANA-4 at C / 10 are shown.
[0450] Use lithium chips (thickness 0.02mm, 1.54cm 2) as the anode and using the above PAQS:SPAN:SP:PTFE:PVDF (6.70 mg, 1.13 cm 2 Electrochemical tests were performed using a two-electrode CR2032 coin-type cell with a cathode. 2 ) as the separator. Various electrolyte formulations were tested, but in this example, it was found that 80 μL of 1M LiTFSI in DME:13DOL (1:1 volume) electrolyte formulation (ANA-4) gave the best cycling data ( Fig.18 ). The cell was cycled at C / 10 with a voltage cutoff of 3.1 V to 1.1 V. The charge and discharge characteristics of the cell at C / 10 are shown in Fig.18 The total discharge capacity of the single cell was found to be 225 mAh / g, which is >40% higher than that of the cathode with PAQS polymer alone.
[0451] Fig.19 The discharge capacity vs. cycle number of Li / / PAQS:SPAN (70:20) cells in ANA-4 at C / 10 is shown. Fig.19 The data show remarkable stability of discharge capacity up to 10 cycles. Coulombic efficiency vs. cycle number is presented in Fig. 20 , which shows 100% Coulombic efficiency up to 10 cycles. Fig. 20 Shown is the coulombic efficiency vs. cycle number of Li / / PAQS:SPAN (70:20) single cells in ANA-4 at C / 10.
[0452] Example 22: PAQS-PBQS random copolymer as cathode active material
[0453] The overall capacity of PAQS can be improved by incorporating lower molecular weight monomers such as benzoquinone (BQ) into the polymer backbone.The synthesis of PAQS-PBQS copolymers is described in Scheme 5 reported in Example 34.
[0454] In this example, a copolymer having 80 mol% PAQS and 20 mol% PBQS was used as the cathode active material. 0.35 g PAQS was first mixed with a mortar and pestle. 0.8 -PBQS 0.2The cathode was prepared by adding 1.70 g of PVDF copolymer and 0.10 g of SP carbon. A solution of 3 wt% PVDF in NMP (1.70 g) was added to the mixed powder (0.45 g) in a plastic cup. The entire mixture was then placed in a Thinky centrifugal mixer and centrifuged at 2000 rpm for 30 seconds for a total of 3 times. In order to obtain the appropriate slurry viscosity and texture, an additional amount of pure NMP was added to the mixture, which was then subsequently centrifuged at 2000 rpm for 30 seconds. A total of 0.2 g of NMP was added to the mixture. An automatic coating machine was used to apply a uniform viscous slurry to a carbon-coated aluminum foil. The coated foil was then dried overnight at 100 ° C under vacuum and stored in it for 4 hours. 2 O and O 2 The final composition of the electrode is shown as PAQS 0.8 -PBQS 0.2 :SP:PVDF (70:20:10 weight ratio).
[0455] Fig.21 The Li / / PAQS in ANA-4 at C / 10 is shown. 0.8 -PBQS 0.2 Voltage curve (charge and discharge characteristics) of a single battery.
[0456] Use lithium chips (thickness 0.02mm, 1.54cm 2 ) as the anode and utilizing the above-mentioned PAQS 0.8 -PBQS 0.2 :SP:PVDF(2.9mg,1.13cm 2 Electrochemical tests were performed using a two-electrode CR2032 coin-type cell with a cathode. 2 ) as the separator. Various electrolyte formulations were tested, but in this example, it was found that 80 μL of 1M LiTFSI in DME:13DOL (1:1 volume) electrolyte formulation (ANA-4) gave the best cycling data ( Fig.21 ). The cell was cycled at C / 10 with a voltage cutoff of 3.2 V to 1.6 V. The charge and discharge characteristics of the cell at C / 10 are shown in Fig. 22 The total discharge capacity of the single cell was found to be 205 mAh / g, which is >25% higher than that of the cathode using the PAQS polymer alone.
[0457] Fig. 22 The Li / / PAQS in ANA-4 at C / 10 is shown. 0.8 -PBQS 0.2 Discharge capacity of a single cell vs. number of cycles.
[0458] Discharge capacity vs. cycle number is shown in Fig. 22 The data show that the discharge capacity decays slightly up to 78 cycles. The Coulombic efficiency vs. cycle number is presented in Fig.23 , which showed a Coulombic efficiency of 98% up to 78 cycles.
[0459] Fig.23 The Li / / PAQS in ANA-4 at C / 10 is shown. 0.8 -PBQS 0.2 Coulombic efficiency of a single cell vs. number of cycles.
[0460] Example 23: PAQS:Sulfur Composite (SC) as Cathode Active Material
[0461] Sulfur cathodes in non-aqueous lithium-sulfur batteries are known to form lithium polysulfides during discharge. The dissolution of polysulfides into the electrolyte and their migration from the cathode to the anode leading to the shuttling phenomenon during charging is one of the major obstacles for lithium-sulfur batteries to become a practical rechargeable battery technology. To demonstrate the advantages of choosing a PAQS:SPAN hybrid cathode, we prepared a PAQS:SC hybrid cathode and cycled the Li / / PAQS:SC single cell following the same protocol as the Li / / PAQS:SPAN single cell in the same electrolyte.
[0462] Sulfur-carbon (SC) composites were purchased from MSE suppliers (product number PO5018). The sulfur content of the composite was reported to be 75 wt%. The cathode was first prepared by mixing the SC composite (0.29 g), PAQS (0.57 g), SP (0.08 g) and KB (0.02 g) together in a mortar and pestle. The entire mixture was placed in a plastic cup and a 3 wt% solution of PVDF in NMP (1.30 g) was added. The cup with the mixture was then placed in a Thinky centrifugal mixer and centrifuged at 2000 rpm for 30 seconds for a total of 3 times. A viscous slurry of uniform appearance was obtained and then coated onto a carbon-coated aluminum foil using an automatic coating machine. The coated foil was then dried overnight at 80°C under vacuum and stored in H 2 O and O 2 The final composition of the electrode was shown to be PAQS:SC:SP:KB:PVDF (57:29:8:2:4 weight ratio).
[0463] Fig.24 The voltage curves (charge and discharge characteristics) of a Li / / PAQS:SC single cell in ANA-4 at C / 10 are shown.
[0464] Use lithium chips (thickness 0.02mm, 1.54cm 2) as the anode and using the above PAQS:SC:SP:KB:PVDF (6.15 mg, 1.13 cm 2 Electrochemical tests were performed using a two-electrode CR2032 coin-type cell with a cathode. 2 ) as separator. An electrolyte formulation (ANA-4) of 80 μL of 1M LiTFSI in DME:13DOL (1:1 volume) was used. The single cell was cycled at C / 10 with a voltage cutoff of 3.2 V to 1.1 V. The charge and discharge characteristics of the single cell at C / 10 are presented in Fig.24 The cycling data show considerable overcharge during charging, which is indicative of a shuttling mechanism.
[0465] Fig.25 Shown are the discharge capacity vs cycle number of Li / / PAQS:SC cells in ANA-4 at C / 10.
[0466] The discharge capacity of a single cell vs. the number of cycles is shown in Fig.25 The data show a considerable decay in discharge capacity up to 17 cycles. Coulombic efficiency vs. cycle number is presented in Fig.26 The data show that the Coulombic efficiency decays significantly with cycling, which is mainly caused by the shuttling mechanism of polysulfides.
[0467] Fig.26 Coulombic efficiency vs cycle number of Li / / PAQS:SC single cells in ANA-4 at C / 10 are shown.
[0468] Example 24: PAQS as cathode active material: elemental sulfur
[0469] In this example, the cathode was first prepared by mixing PAQS (0.57 g), elemental S (0.29 g), SP (0.08 g), and KB (0.02 g) together in a mortar and pestle. The entire mixture was placed in a plastic cup and a 3 wt % solution of PVDF in NMP (1.30 g) was added. The cup with the mixture was then placed in a Thinky centrifugal mixer and centrifuged at 2000 rpm for 30 seconds for a total of 3 times. In order to obtain the appropriate slurry viscosity and texture, an additional amount of pure NMP was added to the mixture, which was then subsequently centrifuged at 2000 rpm for 30 seconds. A total of 0.25 g of NMP was added to the mixture. A viscous slurry of uniform appearance was obtained, which was then coated onto a carbon-coated aluminum foil using an automatic coater. The coated foil was then dried overnight at 80° C. under vacuum and stored in H 2 O and O 2The final composition of the electrode was shown to be PAQS:S:SP:KB:PVDF (57:29:8:2:4 weight ratio).
[0470] Fig. 27 The voltage curves (charge and discharge characteristics) of a Li / / PAQS:S single cell in ANA-4 at C / 10 are shown.
[0471] Use lithium chips (thickness 0.02mm, 1.54cm 2 ) as the anode and using the above PAQS:S:SP:KB:PVDF (6.0 mg, 1.13 cm 2 Electrochemical tests were performed using a two-electrode CR2032 coin-type cell with a cathode. 2 ) as separator. 80 μL of 1M LiTFSI in DME:13DOL (1:1 volume) electrolyte formulation (ANA-4) was used. The single cell was cycled at C / 10 with a voltage cutoff of 3.2 V to 1.1 V. The charge and discharge characteristics of the single cell at C / 10 are presented in Fig. 27 The cycling data show considerable overcharge during charging, suggesting a polysulfide shuttling mechanism.
[0472] Fig.28 Shown are the discharge capacity vs cycle number of Li / / PAQS:S cells in ANA-4 at C / 10.
[0473] The discharge capacity of a single cell vs. the number of cycles is shown in Fig.28 The data show a considerable decay in discharge capacity in only 4 cycles. The Coulombic efficiency data show a significant decay in Coulombic efficiency in only 4 cycles ( Fig.29 ), which is mainly due to the shuttling mechanism of polysulfides.
[0474] Fig.29 Coulombic efficiency vs cycle number of Li / / PAQS:S single cells in ANA-4 at C / 10 are shown.
[0475] Example 25: Comparison between PAQS:SPAN system vs. PAQS:SC or PAQS:S system
[0476] The comparison between SPAN / PAQS and SC composite / PAQS showed the advantages of SPAN. Figures 11 to 14 , Figure 24 to Figure 29The electrochemical performance data of the cells with PAQS:SPAN, PAQS:SC and PAQS:S mixed cathodes and metallic lithium anodes in the same non-aqueous electrolyte (ANA-4) are shown. Fig.11 , Fig.24 , Fig. 27 ) and loop data ( Fig.12 , Fig.25 , Fig.28 ) is that the single cells with PAQS:SPAN hybrid cathodes perform significantly better than the single cells with PAQS:SC and PAQS:S cathodes. Fig.11 As shown, compared with the PAQS:SC composite ( Fig.24 ) and PAQS:S( Fig. 27 ) hybrid cathode, the PAQS:SPAN hybrid cathode of the present invention shows the highest discharge capacity (286 mAh / g). The SPAN material used in the present disclosure is high in sulfur content (up to 40 wt% or more). The conductive material with -S- is embedded in the conductive matrix of pyrolyzed polyacrylonitrile. Due to the embedded nature of active sulfur in the polymer matrix, the battery with PAQS:SPAN cathode shows excellent cycling stability (286 mAh / g) compared to SC and elemental sulfur cathodes. Fig.12 ) and excellent Coulombic efficiency ( Fig.13 ). Both PAQS:SC and PAQS:S cathodes exhibit considerable overcharge, respectively. Fig.24 and Fig. 27 as shown; and low Coulombic efficiency, as shown Fig.26 and Fig.29 The high overcharge and low Coulombic efficiency are believed to be due to the formation of soluble polysulfides during discharge.
[0477] like Fig.14 As shown, the PAQS:SPAN hybrid cathode of the present invention provides a stable high energy density system (>500Wh / kg). Fig.37 Additional data reported in show that PAQS:SPAN hybrid cathodes can provide stable high energy density systems of >650 Wh / kg in some cases.
[0478] Example 26: Synthesis of PAQS
[0479]
[0480] Scheme 1: Organosulfur polymers with a weight average MW ranging from 1,000Da to 2,000,000Da
[0481] Synthesis of PAQS
[0482] To a solution of 2,5-dichloroanthraquinone (25.00 g, 90.22 mmol) in NMP (200 mL) in a 1 L round-bottom flask under argon atmosphere was slowly added Na 2 S.xH 2 O (60%, 11.73g, 90.22mmol). The mixture was stirred at room temperature for 15 minutes under an argon atmosphere and then heated to 150°C for 6 hours. The heating was stopped and their mixture was allowed to cool to room temperature. The precipitate was then filtered out and washed with NMP, then water, and then acetone. The brown solid product of PAQS (22.0g) was dried at 120°C overnight. The formation of PAQS polymer and its purity were verified by elemental analysis and TGA analysis. The data showed that the measured values of C, H and S in PAQS were found to be 67.08%, 2.55% and 12.95%, respectively, which corresponds to C 14 H 6 The empirical formula of S. The approximate calculated values of C, H, and S are 70.57%, 2.54%, and 13.43%, respectively. The measured and calculated values are in close agreement. TGA data show no mass loss up to 420°C.
[0483] Example 27: Synthesis of 36PPAQS
[0484]
[0485] Scheme 2: Synthesis of organosulfur polymer 36PPAQS with a weight average MW ranging from 1,000 Da to 2,000,000 Da
[0486] In an argon-filled glove box, to a solution of 3,6-dibromo-phenanthrenequinone (2.0 g, 5.46 mmol) in NMP (15 mL) in a 40 mL vial was slowly added Na 2 S.xH 2 O (60%, 0.71 g, 5.46 mmol). The mixture was stirred at room temperature for 15 minutes under an argon atmosphere, and then the reaction vial was taken out of the glove box and heated to 110°C. The reaction mixture was heated at 110°C for 16 hours. The heating was then stopped and allowed to cool to room temperature, and a brown solution with some precipitate was observed. 5 mL of EtOH was added to the solution and stirred for 3 hours. A brown precipitate appeared. The precipitate was then filtered off and washed with NMP, then water, and then acetone. The brown solid product of 36PPAQS (1.10 g) was dried at 120°C overnight. The product was characterized by elemental analysis and by TGA. The data showed that the measured values of C, H and S in 36PAQS were found to be 66.55%, 2.68% and 13.21%, respectively, which corresponds to C 14 H 6The empirical formula of S. The approximate calculated values of C, H, and S are 69.98%, 3.36%, and 13.35%, respectively. The measured and calculated values are in close agreement. TGA data show no mass loss up to 400°C.
[0487] 36PPAQS was also synthesized using different reaction solvents such as sulfolane, DMA, DMF, DMSO and sulfolane / NMP mixture following the same steps and conditions as above.
[0488] Example 28: Synthesis of 27PPAQS
[0489]
[0490] Scheme 3: Synthesis of organosulfur polymer 27PPAQS with weight average MW ranging from 1,000 Da to 2,000,000 Da.
[0491] In an argon-filled glove box, to a solution of 2,7-dibromo-phenanthrenequinone (2.0 g, 5.46 mmol) in NMP (15 mL) in a 40 mL vial was slowly added Na 2 S.xH 2 O (60%, 0.71 g, 5.46 mmol). The mixture was stirred at room temperature for 20 minutes under an argon atmosphere, and then the reaction vial was taken out of the glove box and heating to 120°C was started. The reaction mixture was heated at 120°C for 15 hours. The heating was then stopped and allowed to cool to room temperature, and a brown solution with some precipitate was observed. 6 mL of EtOH was added to the solution and stirred for 3 hours. A brown precipitate appeared. The precipitate was then filtered off and washed with NMP, then water, and then acetone. The brown solid product of 27PPAQS (1.0 g) was dried at 110°C overnight. The product was characterized by elemental analysis and by TGA. The data showed that the measured values of C, H and S in 27PAQS were found to be 66.75%, 2.98% and 13.10%, respectively, which corresponds to C 14 H 6 The empirical formula of S. The approximate calculated values of C, H, and S are 69.98%, 3.36%, and 13.35%, respectively. The measured and calculated values are in close agreement. TGA data show no mass loss up to 400°C.
[0492] Example 29: Synthesis of PAQT
[0493] Poly(1,2,5,6-anthracenetetraone sulfide) (PAQT) was synthesized in four steps:
[0494]
[0495] Scheme 4: Synthesis of organosulfur polymers PAQT with a weight average MW ranging from 1,000 Da to 2,000,000 Da
[0496] Example 30: Synthesis of 2,6-dihydroxyanthracene (1)
[0497]
[0498] In a 250 mL two-necked round bottom flask equipped with a stirring bar and the headspace covered with an inert gas, sodium borohydride (3.54 g, 93.5 mmol) was added to a 1 M sodium carbonate solution (78 mL). Next, anthraflavic acid (1, 1.50 g, 6.54 mmol) was added to the reaction mixture in batches, which was then stirred overnight at room temperature. The reaction mixture was poured into cold 6 M hydrochloric acid (13 mL). The aqueous layer was extracted three times with ethyl acetate. The combined organic layers were then washed with saturated sodium bicarbonate solution and washed with anhydrous Na 2 SO 4 The solution was filtered and concentrated under reduced pressure to obtain a light brown powder. The solid was dried at 60°C under vacuum overnight to give 1.3 g of solid (2), 99% yield.
[0499] 1 H-NMR (DMSO-d 6 , 300MHz): δ: 9.67 (s, 2H), 8.15 (s, 2H), 7.84 (d, J = 9Hz, 2H), 7.14 (s, 2H) and 7.09 (d, J = 6.9Hz).
[0500] Example 31: Synthesis of 1,2,5,6-anthracenetetrone (3)
[0501]
[0502] 2.6-dihydroxyanthracene (2,0.5 g, 2.38 mmol) was dissolved in dry THF (48 mL) and purged with argon. The solution was then added in batches to a stirred solution of phenylselenous anhydride (1.71 g, 4.76 mmol) in dry THF (100 mL) (in a three-necked round-bottom flask equipped with a reflux condenser and a thermometer with an argon balloon) under argon. The reaction was heated to 50 ° C for 3 hours and then allowed to cool to room temperature. After storage overnight, the solvent and volatile by-products were removed in vacuo using a rotary evaporator placed in a fume hood to prevent inhalation of volatile selenium by-products. The crude material was stirred at 1,4-dihydroxyanthracene for 3 hours. The mixture was stirred in oxane overnight and filtered to give 460 mg of a red solid (3), 81% yield.
[0503] 1 HNMR (DMSO-d 6 ,300MHz): δ: 8.20 (s, 2H), 7.89 (d, J = 9Hz, 2H), 6.58 and (d, J = 10.2Hz, 2H)
[0504] Example 32: Synthesis of 9,10-dibromo-1,2,5,6-anthracenetetrone (4)
[0505]
[0506] N-bromosuccinimide (0.75, 4.20 mmol) was added once to a solution of 1,2,5,6-anthracentetraone (3, 0.25 g, 1.05 mmol) in acetonitrile (16 mL) in a round-bottom flask equipped with a stirring bar. The resulting mixture was stirred overnight at room temperature. The reaction was allowed to reach room temperature and poured into 30 mL of ice water. The precipitate was filtered, washed with water (3x) and hexane (3x), and dried under high vacuum at 100 ° C to produce 310 mg of dark green solid (4), 75% yield.
[0507] 1 H-NMR (DMSO-d 6 , 300 MHz): δ: 8.26 (d, J = 6.3 Hz, 2H) and 8.05 (d, J = 6.3 Hz, 2H).
[0508] Example 33: Synthesis of poly-anthracenetetraketone sulfide (PAQT) (5)
[0509]
[0510] Anhydrous sodium sulfide (0.020 g, 0.25 mmol) was added to a solution of 4,8-dibromo-1,2,5,6-anthracentetraone (0.10 g, 0.25 mmol) in anhydrous NMP (0.6 mL) in a round bottom flask. The reaction mixture was heated to 100 ° C overnight. The resulting mixture was allowed to reach room temperature and the precipitate was filtered. The precipitate was washed with hot water (3x) and acetone (3x). The precipitate was dried at 110 ° C under high vacuum overnight to produce 80 mg of dark gray solid (PAQT), 100% yield. The product was characterized by elemental analysis. The data showed that the measured values of C, H and S in PAQT were found to be 65.12%, 2.74% and 16.10%, respectively. The approximate calculated values of C, H and S were 63.48%, 2.66% and 16.95%, respectively. The measured and calculated values were in close agreement.
[0511] Example 34: Synthesis of Poly-Anthraquinone-Benzoquinone Sulfide
[0512]
[0513] Scheme 5: Synthesis of random organosulfur copolymers of PAQS-BQ with weight average MW ranging from 1,000 Da to 2,000,000 Da.
[0514] Under argon conditions, 1,5-dichloroanthraquinone (1.0 g, 3.6 mmol), 2,5-dichloro-1,4-benzoquinone (0.2 g, 1.1 mmol), anhydrous NMP (17 mL) and sodium sulfide (0.4 g, 4.7 mmol) were added to the vial. The reaction was stirred at 150 ° C for 16 hours under argon. After completion, the reaction mixture was cooled to room temperature and the precipitate was filtered. The precipitate was washed 3 times with hot water and 3 times with acetone until the washing was clear. The precipitate was dried under vacuum at 120 ° C to produce 0.65 g of orange-brown solid.
[0515] Example 35: Synthesis of Poly-Anthraquinone-Benzoquinone Trisulfide
[0516]
[0517] Scheme 6: Synthesis of random organosulfur copolymers of PAQS3-BQ with a weight average MW ranging from 1,000 Da to 2,000,000 Da
[0518] Under argon conditions, 1,5-dichloroanthraquinone (1.0 g, 3.6 mmol), 2,5-dichloro-1,4-benzoquinone (0.13 g, 0.7 mmol), sulfur (0.28 g, 8.7 mmol), anhydrous NMP (17 mL) and sodium sulfide (0.34 g, 4.3 mmol) were added to the vial. The reaction was stirred at 150 ° C for 16 hours under argon. After completion, the reaction mixture was cooled to room temperature and the precipitate was filtered. The precipitate was washed 3 times with hot water and 3 times with acetone until the washing was clear. The precipitate was dried under vacuum at 120 ° C to produce 1.13 g of dark green solid.
[0519] Example 36: Synthesis of Poly-Anthraquinone-Benzoquinone Pentasulfide
[0520]
[0521] Scheme 7: Synthesis of random organosulfur copolymers of PAQS5-BQ with a weight average MW ranging from 1,000 Da to 2,000,000 Da
[0522] Under argon conditions, 1,5-dichloroanthraquinone (1.0 g, 3.6 mmol), 2,5-dichloro-1,4-benzoquinone (0.13 g, 0.7 mmol), sulfur (0.53 g, 16.6 mmol), anhydrous NMP (17 mL) and sodium sulfide (0.34 g, 4.3 mmol) were added to a vial. The reaction was stirred at 150 ° C for 16 hours under argon. After completion, the reaction mixture was cooled to room temperature and the precipitate was filtered. The precipitate was washed 3 times with hot water and 3 times with acetone until the washing was clear. The precipitate was dried under vacuum at 120 ° C to produce 1.23 g of light green solid.
[0523] Example 37: Synthesis of Sulfurized Polyacrylonitrile (SPAN)
[0524] An exemplary synthesis of a sulfurized carbon matrix polymer from polyacrylonitrile is reported below.
[0525] The sulfurized carbon matrix polymer was synthesized in two steps. First, polyacrylonitrile (PAN, Mw 150,000) was mixed with dry elemental S in a mass ratio of 1:4 and ball milled for 1 hour or up to 3 hours in some cases to ensure uniform mixing. The S:PAN (4:1) mixture was heated in N 2 The filled furnace was heated at 155°C for 2 hours, first for melting the element S and mixing it with the PAN polymer. The furnace temperature was raised to 450°C at a heating rate of 5°C / min, and kept at 450°C for 6 hours to obtain a vulcanized PAN composite material. SPAN was characterized by elemental analysis, and it showed that there were 35.36 wt% S, 48.67 wt% C, 1.08 wt% H and 7.34 wt% N in the vulcanized polymer (SPAN).
[0526] Example 38: Battery made from Li / organic sulfur polymer cathode single cell
[0527] Fig.32 An exemplary arrangement of a plurality of electrochemical cells in a battery as described herein is shown.
[0528] Fig.33 A schematic diagram of an exemplary plurality of electrically connected electrochemical cells according to the present disclosure is shown.
[0529] Example 39: Exemplary Procedure for Preparing an S-Linked Polymer:Sulfurized Carbon Matrix Polymer Cathode
[0530] An exemplary procedure for preparing an S-linked polymer:sulfurized carbon matrix polymer cathode is provided below and can be applied to SPAN or another sulfurized carbon matrix polymer.
[0531] First, the specific ratio of the sulfurized carbon matrix polymer: SP C65 carbon mixture was mixed for 10 minutes by mortar and pestle. The sulfurized carbon matrix polymer: SP C65 mixture was then added to the S-linked quinone polymer PAQS and they were mixed thoroughly using a coffee mixer. The calculated amount of 3 wt% of PVDF or Na-CMC (medium) was added in NMP or H 2 The solution in O was added to the powder mixture of S-linked quinone polymer:sulfurized carbon matrix polymer:SP C65 in a cup sealed with a screw cap. The entire mixture was then placed in a Thinky centrifuge mixer and then mixed at 2000 rpm for 30 seconds to 5 minutes, at least 3 times. The viscous honey-like substance was coated on a carbon-coated aluminum foil. NMP or H 2 O was dried at 80 °C under vacuum.
[0532] Li / / S-linked quinone polymer: another example of a sulfurized carbon-based polymer coin cell
[0533] Example 40: Li / / S-linked quinone polymer:sulfurized carbon matrix polymer:SP-C65:CMC (35:47:11:7) coin cell
[0534] In this example, a mixed mixture of S-linked quinone polymer (PAQS) and sulfurized carbon matrix polymer (sulfurized organosulfur polymer (SPAN)) was used as the cathode active material. The cathode was prepared by first mixing the sulfurized carbon matrix polymer and SP-C65 using a mortar and pestle. The S-linked quinone polymer was then added to the mortar and mixed using a pestle. 3% CMC (medium) was added in H 2 The solution in 0 was added to the mixed mixture of S-linked polymer, sulfurized carbon matrix polymer and SP-C65. The whole mixture was mixed by rotation at 2000 rpm using Thinky for 30 seconds, twice. A viscous slurry of uniform appearance was obtained, which was coated onto a carbon-coated aluminum foil using an automatic coating machine. The coated foil was then dried at 80°C overnight under vacuum and stored in H 2 O and O 2 The final composition of the electrode was shown to be S-linked quinone polymer:sulfurized carbon matrix:SPC65:CMC (35:47:11:7). This combination of mixed polymers is called Gen4 polymer.
[0535] Fig.34 The voltage curves (charge and discharge characteristics) of Li / / Gen4 in ANA-42 at C / 10 are shown.
[0536] Electrochemical tests were performed using lithium chips (thickness 0.02 mm, 1.54 cm2 ) as the anode and the above Gen4 as the cathode. 2 ) as the separator. Various electrolyte formulations were tested, but in this example, it was found that 80 μL of 1.2 M LiFSI in BTFE:TEP (1:3 mol) electrolyte formulation (referred to as ANA-42) gave the best cycling data ( Fig.34 The cells were cycled at C / 10 with a voltage cutoff of 3.2V to 1.0V. When combined with a metallic lithium anode, this Gen4 polymer hybrid blend produced a battery with an average voltage of about 1.9V ( Fig.34 ). The total discharge capacity of the single cell was found to be 350 mAh / g, which is >100% higher than the cathode with PAQS polymer alone. This is a significant improvement in capacity when a mixed blend of S-linked polymer and sulfurized carbon matrix polymer is used as the cathode active material.
[0537] Fig.35 The discharge capacity vs. cycle number of Li / / Gen4 hybrid polymer cells in ANA-42 at C / 10 is shown. The data show remarkable stability of the discharge capacity up to 110 cycles. The Coulombic efficiency vs. cycle number is presented in Fig.36 The total energy density (Wh / kg) of the system vs. the number of cycles is presented in Fig.37 The total energy density was found to be >550Wh / kg or >640Wh / kg and was remarkably stable up to at least 110 cycles.
[0538] Example 41: Gen4 polymer cycles at a higher rate (C / 3)
[0539] The Gen4 blended mixture of polymer cathodes was coated onto carbon-coated aluminum foil as described in Example 40. The coated foil was then dried overnight at room temperature and then dried overnight at 100° C. under vacuum and stored in H 2 O and O 2 The final composition of the electrode was shown to be Gen4:SPC65:CMC (82:11:7 weight ratio).
[0540] Fig.38 Shown are the voltage curves (charge and discharge characteristics) of the Li / / Gen4 mixed polymer cathode in ANA-42 at C / 3.
[0541] The single cell was cycled at C / 3 with a voltage cutoff of 3.2 V to 1.0 V. The charge and discharge characteristics at C / 3 are shown in Fig.38 The total discharge capacity of the single cell was found to be 340 mAh / g, which is also >100% higher than that of the cathode using PAQS polymer alone.
[0542] Fig.39 The discharge capacity vs. cycle number of Li / / Gen4 mixed polymer hybrid cells in ANA-42 at C / 3 is shown. The data show remarkable stability of the discharge capacity up to 210 cycles. The Coulombic efficiency vs. cycle number is presented in Fig.40 , which shows 100% Coulombic efficiency up to 210 cycles.
[0543] Example 42: S-linked quinone polymer: sulfurized carbon matrix polymer: SP-C65 CMC (8:76:10:6)
[0544] In this example, a mixed mixture of S-linked quinone polymer and sulfurized carbon matrix polymer in a weight ratio of 10:90 was used as the cathode active material. Combinations of S-linked quinone polymer and sulfurized carbon matrix polymer in a weight ratio of 20:80 to 5:95 were referred to as Gen5 polymer cathodes. The Gen5 hybrid cathode was prepared as described in Example 40. The coated foil was then dried overnight at room temperature and then dried overnight at 100°C under vacuum and stored in H 2 O and O 2 The final composition of the electrode was shown to be S-linked quinone polymer:sulfurized carbon matrix polymer:SP-C65:CMC (8:76:10:6 weight ratio).
[0545] Fig.41 Shown are the voltage curves (charge and discharge characteristics) of a Li / / Gen5 mixed polymer cathode single cell in ANA-42 at C / 10.
[0546] Use lithium chips (thickness 0.02mm, 1.54cm 2 ) as anode and a two-electrode CR2032 coin-type single cell using the above Gen5 cathode was used for electrochemical testing. 2 ) as the separator. Various electrolyte formulations were tested, but in this example, it was found that 80 μL of 1.2 M LiFSI in BTFE:TEP (1:3 mol) electrolyte formulation (ANA-42) gave the best cycling data ( Fig.41 , Fig.42 and Fig.43). The single cell was cycled at C / 10 with a voltage cutoff of 3.2 V to 1.0 V. The total discharge capacity of the single cell was found to be 598 mAh / g, which is about 240% higher than that of the PAQS polymer alone as the cathode active material.
[0547] Fig.42 The discharge capacity vs. cycle number of Li / / Gen5 polymer in ANA-42 at C / 10 is shown. The data shows remarkable stability of discharge capacity up to 110 cycles. Coulombic efficiency vs. cycle number is presented in Fig.43 , which shows 100% Coulombic efficiency up to 110 cycles. Fig.43 Shown is the coulombic efficiency vs. cycle number of Li / / Gen5 single cells in ANA-42 at C / 10.
[0548] Example 43: PAQS-PBQS random copolymer as cathode active material
[0549] In this embodiment, PAQS is used 0.8 —PBQS 0.2 A random copolymer of PAQS was used as the cathode active material, which was similar to the active material described in Example 22. PAQS was first mixed by using a mortar and pestle 0.8 -PBQS 0.2 The cathode was prepared by mixing 1% PVDF copolymer and SP-C65 carbon. A 3 wt% solution of PVDF in NMP was added to the mixed powder in a plastic cup. The entire mixture was then placed in a Thinky centrifugal mixer and centrifuged at 2000 rpm for 30 seconds for a total of 3 times. The uniform viscous slurry was coated onto a carbon-coated aluminum foil using an automatic coater. The coated foil was then dried at 100°C overnight under vacuum and stored in H 2 O and O 2 The final composition of the electrode is shown as PAQS 0.8 -PBQS 0.2 :SP-C65:PVDF (70:20:10 weight ratio). Use lithium chip (thickness 0.02mm, 1.54cm 2 ) as the anode and utilizing the above-mentioned PAQS 0.8 -PBQS 0.2 :SP-C65:PVDF(2.5mg,1.13cm 2 Electrochemical tests were performed using a two-electrode CR2032 coin-type cell with a cathode. 2) as a separator. Various electrolyte formulations were tested, but in this example, 80 μL of 1M LiTFSI in DME:13DOL (1:1 volume) + 100 mM LiNO 3 The electrolyte formulation (ANA-5) in gives the best cycling data. The single cell was cycled at C / 10 with a voltage cutoff of 3.2 V to 1.6 V. The voltage curve of the single cell is presented in Fig.44 The charge and discharge characteristics and stability of the single cell at C / 10 are shown in Fig.45 The total discharge capacity of the single cell was found to be 225 mAh / g, which is >40% higher than that of the cathode using PAQS polymer alone. Fig.45 As shown in Figure 2, the single cell cycled 608 times without significant capacity decay. The higher capacity and remarkable cycling stability are attributed to the better coating with SP-C65 carbon (which has better conductivity than conventional SP carbon) and the LiNO in the electrolyte. 3 additive.
[0550] Fig.44 The Li / / PAQS in ANA-5 at C / 10 is shown. 0.8 -PBQS 0.2 Voltage curve (charge and discharge characteristics) of a single battery.
[0551] Fig.45 The Li / / PAQS in ANA-5 at C / 10 is shown. 0.8 -PBQS 0.2 Discharge capacity of a single cell versus cycle number. The single cell was cycled up to 608 times without significant capacity decay.
[0552] In summary, redox-active organosulfur polymers and related electrode materials, electrodes, electrochemical cells, batteries, methods and systems are described herein. In particular, the tricyclic compounds have a redox potential of 0.20 V to 3.3 V relative to the Li / Li+ electrode potential under standard conditions. The redox-active organosulfur polymers can be used as cathodes of electrochemical cells comprising a Li anode and a non-aqueous electrolyte. Therefore, the redox-active organosulfur polymers and related electrode materials, electrodes, electrochemical cells, batteries, methods and systems can be used to provide inexpensive, environmentally friendly, safe and / or high-rate batteries in several embodiments, which can be good alternatives to existing batteries for grid storage and other stationary applications.
[0553] Specifically, redox-active S-connected polymers, sulfurized matrices and related composite materials, composition electrode materials, electrodes and related electrochemical cells, batteries, methods and systems are described, wherein the S-connected polymers, sulfurized matrices and related composite materials, composition electrode materials have a redox potential of up to 3.5V relative to the Li / Li+ electrode potential under standard conditions and a capacity of at least 50mAh / g, possibly up to 300mAh / g, up to 400mAh / g, up to 800mAh / g or higher. For example, the S-connected polymers, sulfurized matrices and related composite materials, composition electrode materials have a capacity of 400mAh / g to 800mAh / g or higher. More specifically, redox-active S-connected polymers, sulfurized matrices and related composite materials and compositions are provided as electrode materials for the cathode of an electrochemical cell, the electrochemical cell also comprising a Li anode and a non-aqueous electrolyte.
[0554] The above examples are provided to provide those of ordinary skill in the art with a complete disclosure and description of embodiments of the organosulfur polymers, materials, compositions, systems and methods of the present disclosure, and are not intended to limit the scope of what the inventors regard as their disclosure. All patents and publications mentioned in the specification are indicative of the skill level of those skilled in the art to which the present disclosure pertains.
[0555] The entire disclosure of each document (including patents, patent applications, journal articles including relevant supplementary and / or supporting information sections, abstracts, laboratory manuals, books, or other disclosures) cited in the background, summary, detailed description, and examples is hereby incorporated by reference herein. All references cited in this disclosure are incorporated by reference to the same extent as if each reference was individually incorporated by reference in its entirety. However, if any inconsistency occurs between the cited reference and this disclosure, the disclosure shall prevail.
[0556] The terms and expressions that have been adopted herein are used as terms of description rather than limitation, and the use of such terms and expressions is not intended to exclude any equivalent forms of the features shown and described or portions thereof, but it should be recognized that various modifications can be made within the scope of the disclosure claimed. Therefore, it should be understood that although the present disclosure has been specifically disclosed through preferred embodiments, exemplary embodiments and optional features, those skilled in the art may make modifications and changes to the concepts disclosed herein, and such modifications and changes are considered to be within the scope of the present disclosure as defined by the appended claims.
[0557] It should also be understood that the terms used herein are used only for the purpose of describing specific embodiments and are not intended to be limiting. Unless the content clearly dictates otherwise, nouns as used in this specification and the appended claims without quantifiers include plural referents. Unless the content clearly dictates otherwise, the term "plurality" includes two or more referents. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the present disclosure belongs.
[0558] As used herein, the term "alkyl" refers to a linear, branched or cyclic saturated hydrocarbon group, usually but not necessarily containing 1 to about 15 carbon atoms or 1 to about 6 carbon atoms, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, octyl, decyl, etc., and cycloalkyl, such as cyclopentyl, cyclohexyl, etc. Usually, although not necessarily, the alkyl group herein contains 1 to about 15 carbon atoms. The term "cycloalkyl" means a cyclic alkyl group usually having 4 to 8 or 5 to 7 carbon atoms. The term "substituted alkyl" refers to an alkyl group substituted with one or more substituents, and the terms "heteroatom-containing alkyl" and "heteroalkyl" refer to an alkyl group in which at least one carbon atom is replaced by a heteroatom. If not otherwise specified, the terms "alkyl" and "lower alkyl" include linear, branched, cyclic, unsubstituted, substituted and / or heteroatom-containing alkyl and lower alkyl groups, respectively.
[0559] As in "heteroatom-containing alkyl", the term "heteroatom-containing" refers to an alkyl group in which one or more carbon atoms are replaced by atoms other than carbon, such as nitrogen, oxygen, sulfur, phosphorus or silicon, typically nitrogen, oxygen or sulfur. Similarly, the term "heteroalkyl" refers to a heteroatom-containing alkyl substituent, the term "heterocycle" refers to a heteroatom-containing cyclic substituent, the terms "heteroaryl" and "heteroaromatic" refer to heteroatom-containing "aryl" and "aromatic" substituents, respectively, and the like. It should be noted that a "heterocycle" group or compound may or may not be aromatic, and furthermore a "heterocycle" may be monocyclic, bicyclic or polycyclic, as described above with respect to the term "aryl". Examples of heteroalkyl groups include alkoxyaryl, alkylsulfanyl-substituted alkyl, N-alkylated aminoalkyl, and the like. Examples of heteroaryl substituents include pyrrolyl, pyrrolidinyl, pyridinyl, quinolinyl, indolyl, pyrimidinyl, imidazolyl, 1,2,4-triazolyl, tetrazolyl, and the like, and examples of heteroatom-containing alicyclic groups are pyrrolidino, morpholinyl, piperazinyl, piperidinyl, and additional substituents that can be recognized by the skilled artisan.
[0560] The term "alkoxy" as used herein means an alkyl group bonded through a single terminal ether linking group; that is, an "alkoxy" group may be represented as -O-alkyl, wherein alkyl is as defined above. A "lower alkoxy" group means an alkoxy group containing from 1 to 6 carbon atoms. Similarly, "alkenyloxy" and "lower alkenyloxy" refer to alkenyl and lower alkenyl groups, respectively, bonded through a single terminal ether linking group, and "alkynyloxy" and "lower alkynyloxy" refer to alkynyl and lower alkynyl groups, respectively, bonded through a single terminal ether linking group.
[0561] Unless otherwise indicated, the term "aryl" as used herein refers to an aromatic substituent comprising a single aromatic ring or multiple aromatic rings, which are fused together, directly connected or indirectly connected (so that different aromatic rings are bonded to a common group such as a methylene or ethylene moiety). The aryl group can contain 5 to 24 carbon atoms, or the aryl group contains 5 to 14 carbon atoms. Exemplary aryl groups include one aromatic ring or two fused or connected aromatic rings, such as phenyl, naphthyl, biphenyl, diphenyl ether, diphenylamine, benzophenone, etc. "Substituted aryl" refers to an aryl moiety substituted with one or more substituents, and the terms "heteroatom-containing aryl" and "heteroaryl" refer to aryl substituents in which at least one carbon atom is replaced by a heteroatom, as will be described in further detail below.
[0562] The terms "cyclic," "cyclo-," and "ring" refer to alicyclic or aromatic groups that may or may not be substituted and / or contain heteroatoms, and may be monocyclic, bicyclic, or polycyclic. The term "alicyclic" is used in the conventional sense to refer to aliphatic cyclic moieties, as opposed to aromatic cyclic moieties, and may be monocyclic, bicyclic, or polycyclic.
[0563] The term "isomer" as used herein refers to heterocyclic aromatic groups having the same core molecule but which may differ in atomic connectivity and / or position of unsaturation, and is intended to include all possible structural variations. For example, as shown below, "pyrrole isomers" refer to all possible substituted variations of 1H-pyrrole and 2H-pyrrole; "indole isomers" refer to all possible substituted variations of 3H-indole, 1H-indole, and 2H-isoindole, and so on:
[0564]
[0565] Likewise, as shown below, "triazole isomers" refers to all possible substituted variations of 1,2,4-triazole and 1,2,3-triazole; " "Oxadiazole isomers" refers to 1,2,5- Oxadiazole and 1,2,3- All possible substituted variations of oxadiazole, etc.:
[0566]
[0567] The terms "halo," "halogen," and "halide" are used in the conventional sense to refer to chloro, bromo, fluoro, or iodo substituents or ligands.
[0568] The term alkylene as used herein refers to an alkanediyl group that is a divalent saturated aliphatic group having two carbon atoms as points of attachment, a linear or branched, cyclic, cyclic or acyclic structure. Exemplary alkylene groups include propane-1,2-diyl (-CH(CH3)CH2-) or propane-1,3-diyl (-CH2CH2CH2-).
[0569] The term alkenylene refers to an alkene diyl group which is a divalent unsaturated aliphatic group having two carbon atoms as points of attachment, a linear or branched, cyclic, cyclic or acyclic structure, at least one non-aromatic carbon-carbon double bond. Exemplary alkylene groups include 2-butene-1,4-diyl (-CH2CH=CHCH2-).
[0570] The term alkynylene refers to an alkynyl diyl group that is a divalent unsaturated aliphatic group having two carbon atoms as points of attachment, a linear or branched, cyclic, cyclic or acyclic structure, and at least one non-aromatic carbon-carbon triple bond. Exemplary alkylene groups include 2-butyne-1,4-diyl (-CH2C≡CCH2-).
[0571] The term "substituted" as in "substituted alkyl", "substituted aryl", etc., means that at least one hydrogen atom bonded to a carbon (or other) atom in an alkyl, aryl or other moiety is replaced by one or more non-hydrogen substituents.
[0572] Examples of such substituents include, but are not limited to, functional groups such as halogen, hydroxyl, thiol, C1-C24 alkoxy, C2-C24 alkenyloxy, C2-C24 alkynyloxy, C5-C24 aryloxy, C6-C24 aralkyloxy, C6-C24 alkaryloxy, acyl (including C2-C24 alkylcarbonyl (-CO-alkyl) and C6-C24 arylcarbonyl (-CO-aryl)), acyloxy (-O-acyl, including C2-C24 alkylcarbonyloxy (-O-CO-alkyl) and C6-C24 arylcarbonyloxy (-O-CO-aryl)), C2-C24 alkoxycarbonyl (-(CO)-O-alkyl), C6-C24 aryloxycarbonyl (-(CO)-O-aryl), halocarbonyl (-CO)-X,wherein X is a halogen), C2-C24 alkyl carbonate (-O-(CO)-O-alkyl), C6-C24 aryl carbonate (-O-(CO)-O-aryl), carboxyl (-COOH), carboxylate (COO-), carbamoyl (-(CO)-NH2), mono-(C1-C24 alkyl)-substituted carbamoyl (-(CO)-NH(C1-C24 alkyl)), di-(C1-C24 alkyl)-substituted carbamoyl (-(CO)-N(C1-C24 alkyl)2), mono-(C5-C24 aryl)-substituted carbamoyl (-(CO)-NH-aryl), di-( C5-C24 aryl)-substituted carbamoyl (-(CO)-N(C5-C24 aryl)2), di-N-(C1-C24 alkyl), N-(C5-C24 aryl)-substituted carbamoyl, thiocarbamoyl (-(CS)-NH2), mono-(C1-C24 alkyl)-substituted thiocarbamoyl (-(CO)-NH(C1-C24 alkyl)), di-(C1-C24 alkyl)-substituted thiocarbamoyl (-(CO)-N(C1-C24 alkyl)2), mono-(C5-C24 aryl)-substituted thiocarbamoyl (-(CO)-NH-aryl) , di-(C5-C24 aryl)-substituted thiocarbamoyl (-(CO)-N(C5-C24 aryl)2), di-N-(C1-C24 alkyl), N-(C5-C24 aryl)-substituted thiocarbamoyl, urea (-NH-(CO)-NH2), cyano (-C≡N), cyanato (-OC≡N), thiocyanato (-SC≡N), formyl (-(CO)-H), thioformyl ((CS)-H), amino (-NH2), mono-(C1-C24 alkyl)-substituted amino, di-(C1-C24 alkyl)-substituted amino, mono-(C5-C24 aryl) -substituted amino, di-(C5-C24 aryl)-substituted amino, C2-C24 alkylamide (-NH-(CO)-alkyl), C6-C24 arylamide (-NH-(CO)-aryl), imino (-CR=NH, wherein R=hydrogen, C1-C24 alkyl, C5-C24 aryl, C6-C24 alkylaryl, C6-C24 arylalkyl, etc.), C2-C20 alkylimino (CR=N(alkyl), wherein R=hydrogen, C1-C24 alkyl, C5-C24 aryl, C6-C24 alkylaryl, C6-C24 arylalkyl, etc.), arylimino (-CR=N(aryl),wherein R = hydrogen, C1-C20 alkyl, C5-C24 aryl, C6-C24 alkylaryl, C6-C24 aralkyl, etc.), nitro (-NO2), nitroso (-NO), sulfo (-SO2-OH), sulfonic acid (-SO2-O-), C1-C24 alkylsulfanyl (-S-alkyl; also known as "alkylthio"), C5-C24 arylsulfanyl (-S-aryl; also known as "arylthio"), C1-C24 alkylsulfinyl (-(SO)-alkyl), C5-C24 arylsulfinyl (-(SO)-aryl), C1-C24 alkylsulfonyl (-SO2-alkyl), C5-C24 arylsulfonyl (-SO2-aryl), boryl (-BH2), dihydroxyboryl (-B(OH)2), borate (-B(OR)2, wherein R is alkyl alkyl or other hydrocarbon groups), phosphono (-P(O)(OH)2), phosphonate (-P(O)(O-)2), phosphinate (-P(O)(O-))), phosphate (-PO2), phosphino (-PH2), silyl (-SiR3, wherein R is hydrogen or hydrocarbon group) and siloxy (-O-silyl); and hydrocarbon moieties C1-C24 alkyl (e.g., C1-C12 alkyl and C1-C6 alkyl), C2-C24 alkenyl (e.g., C2-C12 alkenyl and C2-C6 alkenyl), C2-C24 alkynyl (e.g., C2-C12 alkynyl and C2-C6 alkynyl), C5-C24 aryl (e.g., C5-C14 aryl), C6-C24 alkylaryl (e.g., C6-C16 alkylaryl), and C6-C24 arylalkyl (e.g., C6-C16 arylalkyl). ,
[0573] The term "acyl" refers to a substituent having the formula -(CO)-alkyl, -(CO)-aryl or -(CO)-aralkyl, and the term "acyloxy" refers to a substituent having the formula -O(CO)-alkyl, -O(CO)-aryl or -O(CO)-aralkyl, wherein "alkyl", "aryl" and "aralkyl" are as defined above.
[0574] The term "alkylaryl" refers to an aryl with an alkyl substituent, and the term "arylalkyl" refers to an alkyl with an aryl substituent, wherein "aryl" and "alkyl" are as defined above. In some embodiments, alkylaryl and arylalkyl contain 6 to 24 carbon atoms, and particularly alkylaryl and arylalkyl contain 6 to 16 carbon atoms. Alkylaryl includes, for example, p-methylphenyl, 2,4-dimethylphenyl, p-cyclohexylphenyl, 2,7-dimethylnaphthyl, 7-cyclooctylnaphthyl, 3-ethyl-cyclopenta-1,4-diene, etc. The example of arylalkyl includes, but is not limited to, benzyl, 2-phenyl-ethyl, 3-phenyl-propyl, 4-phenyl-butyl, 5-phenyl-pentyl, 4-phenylcyclohexyl, 4-benzylcyclohexyl, 4-phenylcyclohexylmethyl, 4-benzylcyclohexylmethyl, etc. The terms "alkylaryloxy" and "aralkyloxy" refer to substituents of the formula -OR, wherein R is alkylaryl or aralkyl, respectively, as just defined.
[0575] The term "periodic table" refers to the version of the IUPAC Periodic Table of the Elements dated 28 November 2016.
[12]
[0576] When using Markush group or other grouping in this article, all individual members of the group and all combinations and possible sub-combinations of the group are intended to be included in the present disclosure separately. Unless otherwise stated, each combination of components or materials described or illustrated herein can be used to implement the present disclosure. It will be understood by those of ordinary skill in the art that methods, device elements and materials other than those specifically illustrated can be adopted in the practice of the present disclosure without resorting to excessive experiments. All functional equivalents known in the art of any such method, device element and material are intended to be included in the present disclosure. Whenever a range is given in the specification, such as a temperature range, a frequency range, a time range or a composition range, all intermediate ranges and all sub-ranges, and all individual values included in a given range are intended to be included in the present disclosure. Any one or more individual members of the range or group disclosed herein can be excluded from the claims of the present disclosure. The disclosure illustratively described herein can be appropriately practiced in the absence of any one or more elements, one or more restrictions not specifically disclosed herein.
[0577] "Optional" or "optionally" means that the subsequently described situation may or may not occur, so that the description includes examples of situations that occur and examples of situations that do not occur according to the guidance provided by the present disclosure. For example, the phrase "optionally substituted" means that non-hydrogen substituents may or may not be present on a given atom, and therefore, the description includes structures in which non-hydrogen substituents are present and structures in which non-hydrogen substituents are not present. It should be understood that the phrase "optionally substituted" is used interchangeably with the phrase "substituted or unsubstituted". Unless otherwise specified, an optionally substituted group can have a substituent at each substitutable position of the group, and when more than one position in any given structure can be substituted by more than one substituent selected from a specified group, the substituent at each position can be the same or different. Considering the desired characteristics of the compounds according to the present disclosure, and considering the characteristics of achieving the formation of stable or chemically feasible compounds, the envisioned substituent combination can be identified. The term "stable" as used herein refers to a compound that is substantially unchanged when subjected to conditions that allow its production, detection, and in certain embodiments, its recovery, purification, and use for one or more purposes disclosed herein.
[0578] A number of embodiments of the present disclosure have been described. The specific embodiments provided herein are examples of useful embodiments of the present disclosure, and it will be apparent to those skilled in the art that a large number of variations of the devices, device components, and method steps set forth in this specification may be used to implement the present disclosure. It will be apparent to those skilled in the art that the methods and devices useful for the present method may include a large number of optional components and processing elements and steps.
[0579] In summary, in several embodiments, described herein are organosilicon compounds, related complexes that allow for fluorocarbon or olefin-based reactions, and in particular, polymerization of olefins to produce polyolefin polymers, and related methods and systems.
[0580] In particular, it will be appreciated that various modifications may be made without departing from the spirit and scope of the present disclosure. Accordingly, other implementations are within the scope of the following claims.
[0581] References
[0582] 1.IUPAC.Compendium of chemical terminology(the "Gold Book").2nded.1997: Blackwell Science Oxford.
[0583] 2. Goldbook, i. quinones. 2014; Available from: https: / / goldbook.iupac.org / terms / view / Q05015.
[0584] 3. Patai, S. and Z. Rappoport, The Quinonoid Compounds vol 1. 1988. John Wilcy & Sons Ltd., Hoboken.
[0585] 4. Patai, S. and Z. RaPpoport, The Quinonoid Compounds, vol 2. 1988, John Wiley & Sons Ltd., Hoboken.
[0586] 5. Wikipedia - Quinone. Quinone 2022; Available from: https: / / en.wikipedia.org / wiki / Quinone.
[0587] 6. Wang, J., et al., A novel conductive polymer - sulfur composite cathode material for rechargeable lithium batteries. Advanced materials, 2002. 14(13 - 14): p. 963 - 965.
[0588] 7. Ahmcd, M.S., ct al., Multiscalc understanding of covalently fixed sulfur - polyacrylonitrile composite as advanced cathode for metal - sulfur batteries. Advanced Science, 2021. 8(21): p. 2101123.
[0589] 8. Shadikc, Z., ct al., Review on organosulfur materials for rechargeable lithium batteries. Materials Horizons, 2021. 8(2): p. 471 - 500.
[0590] 9.Pan, Z., et al., Progress and perspectives of organosulfur for lithium-sulfur batteries. Advanced Energy Materials, 2022. 12(8): p. 2103483.
[0591] 10.Zhang, S.S., Understanding of sulfurized polyacrylonitrile for superior performance lithium / sulfur battery. Energies, 2014. 7(7): p. 4588-4600.
[0592] 11.Yu, X.-g., et al., Lithium storage in conductive sulfur-containing polymers. Journal of Electroanalytical Chemistry, 2004. 573(1): p. 121-128.
[0593] 12.IUPAC. Periodic Table. 2016; Available from: iupac.org / wp-content / uploads / 2015 / 07 / IUPAC_Periodic_Table-28Nov 16.pdf.
Claims
1. An S-linked quinone homopolymer represented by formula (I) -[M-S p ]- m (I) in M is a redox-active monomeric quinone moiety having a redox potential of 0.5 V to 3.5 V relative to the Li / Li+ electrode potential under standard conditions, p refers to the number of sulfur atoms attached to the redox-active monomeric quinone moiety M, and p ranges from 1 to 5, When p is 1, S p is a sulfide, or when p is 2 to 5, S p For polysulfide, m ranges from 5 to 10,000, wherein the S-linked quinone polymer has a weight average molecular weight of at least 1,000 Daltons or a weight average MW ranging from 2000 Daltons to 2,000,000 Daltons, 10,000 Daltons to 1,500,000 Daltons, 100,000 Daltons to 1,000,000 Daltons, and a solubility in tetrahydrofuran (THF) equal to or less than 1.0 micrograms / mL at 21°C at 1 atmosphere.
2. The S-linked quinone homopolymer of claim 1, wherein the redox-active monomeric quinone portion comprises a structure represented by formula (III): Where R 1 , R 2 , R 3 and R 4 Each is independently empty; H; Sp, where p ranges from 1 to 5; F; Cl; Br; I; CF3; a linear or branched, substituted or unsubstituted C1-C4 aliphatic group; an aromatic, heteroaromatic, non-aromatic ring; or a non-aromatic heterocyclic ring containing a substituent containing 4 to 12 carbon atoms and 0 to 4 heteroatoms, wherein the heteroatoms are selected from O, N and S, R 1 and R 2 Together and / or R 3 and R 4 together are part of an aromatic or aliphatic cyclic structure, wherein when the associated R 1 , R 2 , R 3 or R 4 When empty, the dashed line ----- represents empty or a single bond to the quinone ring carbon.
3. The S-linked quinone homopolymer of claim 2, wherein the redox-active monomeric quinone moiety is S-linked, wherein the S-linked redox-active monomeric quinone is represented by formula (IIIA) and formula (IIIB) Formula (IIIA) Formula (IIIB).
4. The S-linked quinone homopolymer of claim 1, wherein the redox-active monomeric quinone portion comprises a structure represented by formula (IV): Where R 1 , R 2 , R 3 and R 4 Each independently empty; H; S p , wherein p ranges from 1 to 5; F; Cl; Br; I; CF3; a linear or branched, substituted or unsubstituted C1-C4 aliphatic group; an aromatic, heteroaromatic, non-aromatic ring; or a non-aromatic heterocyclic ring containing a substituent containing 4 to 12 carbon atoms and 0 to 4 heteroatoms, wherein the heteroatoms are selected from O, N and S, R 1 and R 2 Together and / or R 3 and R 4 together are part of an aromatic or aliphatic ring structure, When the relevant R 1 , R 2 , R 3 or R 4 When empty, the dashed line ----- represents empty or a single bond to the quinone ring carbon.
5. The S-linked quinone homopolymer of claim 4, wherein the redox-active monomeric quinone moiety is S-linked, wherein the S-linked redox-active monomeric quinone is represented by any of the S-linked monomeric moieties of formula (IVA), formula (IVB), or formula (IVC) 6. An S-linked quinone copolymer represented by formula (II) -[M1-S p1 ] m1 -co-[M2-S p2 ]- m2 (II) in M1 and M2 are each a redox-active monomeric quinone moiety comprising a redox potential of 0.5 V to 3.5 V relative to the Li / Li+ electrode potential under standard conditions, p1 and p2 each independently refer to the number of sulfur atoms connected to the redox-active monomeric quinone moiety M1 and the monomeric quinone moiety M2, respectively, and p1 and p2 each independently range from 1 to 5, When p1 is 1, S p1 is a sulfide, or when p1 is 2 to 5, S p1 For polysulfide, When p2 is 1, S p2 is a sulfide, or when p2 is 2 to 5, S p2 For polysulfide, m1 and m2 each independently range from 5 to 5,000, optionally the ratio of m1 to m2 ranges from 1:50 to 1:1, 1:20 to 1:2, 1:6 to 1:3 or 1:5 to 1:4, wherein the S-linked quinone copolymer of formula (II) has a weight average molecular weight ranging from 1,000 Daltons to 2,000,000 Daltons, or a weight average MW ranging from 2000 Daltons to 2,000,000 Daltons, 10,000 Daltons to 1,500,000 Daltons, 100,000 Daltons to 1,000,000 Daltons, and a solubility in tetrahydrofuran (THF) equal to or less than 1.0 micrograms / mL at 21°C at 1 atmosphere.
7. The S-linked quinone copolymer of claim 6, wherein the redox-active monomeric quinone moieties M1 and the monomeric quinone moieties M2 are arranged in a random copolymer, a block copolymer, or an alternating copolymer. 8 . The S-linked quinone copolymer of claim 7 , wherein the redox active monomeric quinone portion M1 and the redox active monomeric quinone portion M2 are in a random copolymer arrangement.
9. The S-linked quinone copolymer according to claim 6, wherein the redox-active monomeric quinone portion M1 and the redox-active monomeric quinone portion M2 are independently represented by any one of formula (III) and formula (IV): Wherein R of formula (III) and formula (IV) 1 , R 2 , R 3 and R 4 Each independently empty; H; S p , wherein p ranges from 1 to 5; F; Cl; Br; I; CF3; a linear or branched, substituted or unsubstituted C1-C4 aliphatic group; an aromatic, heteroaromatic, non-aromatic ring; or a non-aromatic heterocyclic ring containing a substituent containing 4 to 12 carbon atoms and 0 to 4 heteroatoms, wherein the heteroatoms are selected from O, N and S, R 1 and R 2 Together and / or R 3 and R 4 together are part of an aromatic or aliphatic ring structure, When the relevant R 1 , R 2 , R 3 or R 4 When empty, the dashed line ----- represents empty or a single bond to the quinone ring carbon.
10. The S-linked quinone copolymer of claim 9, wherein the redox-active monomeric quinone moiety M1 and the redox-active monomeric quinone moiety M2 are S-linked, wherein the S-linked redox-active monomeric quinone moiety M1 and the S-linked redox-active monomeric quinone moiety M2 are independently selected from any one of the S-linked monomeric moieties of formula (IIIA), formula (IIIB), formula (IVA), formula (IVB), and formula (IVC) 11. The S-linked quinone copolymer of claim 10, wherein the S-linked redox-active monomeric quinone moiety M1 is represented by formula (IIIA), and the S-linked redox-active monomeric quinone moiety M2 is represented by any one of the S-linked monomeric moieties of Formula (IIIB), Formula (IVA), Formula (IVB), and Formula (IVC), wherein the molar ratio of the S-linked monomeric moiety of Formula (IIIA) to the S-linked monomeric moiety of any of Formula (IIIB), Formula (IVA), Formula (IVB), and Formula (IVC) ranges from 1:50 to 1:1, 1:20 to 1:2, 1:6 to 1:3, or 1:5 to 1:
4.
12. The S-linked quinone copolymer of claim 11, wherein the molar ratio of the S-linked monomer moiety M1 of formula (IIIA) to the S-linked monomer moiety M2 of formula (IIIB), formula (IVA), formula (IVB) or formula (IVC) is 1:
4.
13. The S-linked quinone copolymer of claim 11, wherein the S-linked redox-active monomeric quinone moiety M2 of formula (II) is represented by formula (IIIB) 14. The S-linked quinone copolymer according to claim 13, wherein the molar ratio of the S-linked monomeric moiety of formula (IIIA) to the S-linked monomeric moiety of formula (IIIB) is 1:
4.
15. A sulfided carbon matrix represented by formula (V), wherein Q is a bonded sp2 carbon atom (C) or nitrogen (N), wherein Indicates a single bond or a double bond, S p represents a polysulfide and p ranges from 2 to 8, wherein the sulfided carbon matrix has a weight average MW ranging from 2000 Daltons to 2,000,000 Daltons, or a weight average MW ranging from 2000 Daltons to 2,000,000 Daltons, 10,000 Daltons to 1,500,000 Daltons, 100,000 Daltons to 1,000,000 Daltons, wherein the sulfurized carbon matrix has a sulfur content equal to or greater than 5 wt % and less than 20 wt %, equal to or greater than 20 wt % and less than 40 wt %, equal to or greater than 40 wt % and less than 60 wt %, equal to or greater than 60 wt % and less than 70 wt %, equal to or greater than 70 wt % and less than 80 wt %, based on the total weight of the sulfurized carbon matrix.
16. The sulfurized carbon matrix according to claim 15, wherein the sulfurized carbon matrix of formula (V) can be selected from any one of the following: sulfurized SPAN (11), covalent triazine framework (S-CTF-1) (12), covalent triazine framework (S-CTF-1) (13), poly(sulfur random-1,3-diisopropylbenzene) (poly(Sr-DIB)) (14), S-BOP (15), carbon / polymer sulfur (C / PS) composites (16), covalently grafted polysulfide graphene nanocomposites (PolySGN, 17) and graphene-supported cross-linked sulfur copolymer nanoparticles, cp(S-TTCA)@rGO-80 (18) or any combination thereof.
17. A redox-active composition comprising at least one S-linked quinone homopolymer according to claim 1, and one or more sulfurized carbon substrates represented by formula (V), and optionally additives, wherein Q is a bonded sp2 carbon atom (C) or nitrogen (N), wherein Indicates a single bond or a double bond, S p represents a polysulfide and p ranges from 2 to 8, wherein the sulfided carbon matrix has a weight average MW ranging from 2000 Daltons to 2,000,000 Daltons, or a weight average MW ranging from 2000 Daltons to 2,000,000 Daltons, 10,000 Daltons to 1,500,000 Daltons, 100,000 Daltons to 1,000,000 Daltons, wherein the sulfurized carbon matrix has a sulfur content equal to or greater than 5 wt % and less than 20 wt %, equal to or greater than 20 wt % and less than 40 wt %, equal to or greater than 40 wt % and less than 60 wt %, equal to or greater than 60 wt % and less than 70 wt %, equal to or greater than 70 wt % and less than 80 wt %, based on the total weight of the sulfurized carbon matrix.
18. A redox-active composite material comprising at least one S-linked quinone homopolymer according to claim 1, and at least one sulfided carbon matrix according to claim 15, and / or a combination according to claim 17.
19. A redox-active composite material comprising at least one S-linked quinone polymer selected from the S-linked quinone homopolymer according to claim 1, and one or more sulfurized carbon matrices represented by formula (V), wherein Q is a bonded sp2 carbon atom (C) or nitrogen (N), wherein Indicates a single bond or a double bond, S p represents a polysulfide and p ranges from 2 to 8, wherein the sulfided carbon matrix has a weight average MW ranging from 2000 Daltons to 2,000,000 Daltons, or a weight average MW ranging from 2000 Daltons to 2,000,000 Daltons, 10,000 Daltons to 1,500,000 Daltons, 100,000 Daltons to 1,000,000 Daltons, wherein the sulfurized carbon matrix has a sulfur content of equal to or greater than 5 wt % and less than 20 wt %, equal to or greater than 20 wt % and less than 40 wt %, equal to or greater than 40 wt % and less than 60 wt %, equal to or greater than 60 wt % and less than 70 wt %, equal to or greater than 70 wt % and less than 80 wt %, based on the total weight of the sulfurized carbon matrix, The weight ratio of the S-linked quinone polymer to the sulfided carbon matrix ranges from 20:1 to 1:20, 10:1 to 1:10, 9:1 to 3:2, or 6:1 to 2:1, or is 1:
1.
20. The redox-active composite material of claim 19, wherein the S-linked quinone homopolymer is selected from 2,5-S-linked polyanthraquinone (PAQS), 3,6-S-linked polyphenanthrenequinone (36PPAQS), 2,7-S-linked polyphenanthrenequinone (27PPAQS) and 9,10-S-linked 1,2,5,6-polyanthracentetraone (PAQT).
21. The redox-active composite material of claim 20, wherein the sulfided carbon matrix is SPAN.
22. The redox-active composite material of claim 19, further comprising an additive such as a binder, and a conductive additive, wherein the binder may be optionally selected from one of the following: poly(vinylidene fluoride), poly(tetrafluoroethylene), sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid (PAA), polyvinyl alcohol (PVA), polyethylene glycol (PEG), polyethylene oxide (PEO), polyamide-imide (PAI) or any combination thereof, wherein the conductive additive is selected from one of the following: graphite, carbon black, acetylene black, Super-P carbon, nickel powder, various Super-P carbons and KB or any combination thereof.
23. The redox active composite material of claim 22, wherein the additive comprises a binder, wherein the binder is present in an amount of 1 wt % to 20 wt % of the redox active composite material, and the conductive additive is present in an amount of 5 wt % to 70 wt % of the redox active composite material.
24. A cathode material comprising the redox active composition of claim 17.
25. The cathode material of claim 24, wherein the weight ratio of the S-linked quinone polymer to the sulfided carbon matrix ranges from 20:1 to 1:20, 10:1 to 1:10, 9:1 to 3:2, or 6:1 to 2:1, or is 1:
1.
26. A method for providing a cathode material, the method comprising At least one S-linked quinone polymer according to claim 1, at least one sulfurized carbon matrix represented by formula (V), and optionally a conductive additive are combined to provide a redox composition and / or a redox composite material configured to be contacted with a non-aqueous electrolyte or an aqueous electrolyte of an electrochemical cell, wherein Q is a bonded sp2 carbon atom (C) or nitrogen (N), wherein Indicates a single bond or a double bond, S p represents a polysulfide and p ranges from 2 to 8, wherein the sulfided carbon matrix has a weight average MW ranging from 2000 Daltons to 2,000,000 Daltons, or a weight average MW ranging from 2000 Daltons to 2,000,000 Daltons, 10,000 Daltons to 1,500,000 Daltons, 100,000 Daltons to 1,000,000 Daltons, wherein the sulfurized carbon matrix has a sulfur content equal to or greater than 5 wt % and less than 20 wt %, equal to or greater than 20 wt % and less than 40 wt %, equal to or greater than 40 wt % and less than 60 wt %, equal to or greater than 60 wt % and less than 70 wt %, equal to or greater than 70 wt % and less than 80 wt %, based on the total weight of the sulfurized carbon matrix.
27. The method of claim 25, wherein the at least one S-linked quinone polymer and the at least one sulfurized carbon matrix are homogeneously mixed.
28. The method of claim 26, wherein the at least one S-linked quinone polymer and the at least one sulfided carbon matrix can be combined in any configuration that allows electrical connection between the at least one S-linked quinone polymer and the at least one sulfided carbon matrix, and when the cathode material is contained in an electrochemical cell, the configuration also enables contact with a non-aqueous electrolyte.
29. The method of claim 26, wherein the combining is performed to provide a cathode material as described herein, wherein the weight ratio of the S-linked quinone polymer to the sulfided carbon matrix ranges from 20:1 to 1:20, 10:1 to 1:10, 9:1 to 3:2, or 6:1 to 2:1, or is 1:
1.
30. A cathode material obtained by the method according to claim 26.
31. A system for providing a cathode material described as comprising at least one S-linked quinone homopolymer according to claim 1, at least one sulfided carbon matrix according to claim 15, and optionally an additive for use in combination to provide a cathode material.
32. A method for preparing an S-linked quinone homopolymer, the method comprising Providing a redox-active monomer quinone monomer X1-M-X2, wherein X1 and X2 represent leaving groups, Provide a sulfide Sp source, Contacting the redox-active monomeric quinone monomer X1-M-X2 with the sulfide Sp source under suitable conditions and for a sufficient period of time to provide an S-linked quinone polymer represented by formula (I) -[M-S p ]- m (I) in M is a redox-active monomeric quinone moiety having a redox potential of 0.5 V to 3.5 V relative to the Li / Li+ electrode potential under standard conditions, p refers to the number of sulfur atoms attached to the redox-active monomeric quinone moiety M, and p ranges from 1 to 5, When p is 1, S p is a sulfide, or when p is 2 to 5, S p For polysulfide, m ranges from 5 to 10,000, wherein the S-linked quinone polymer has a weight average molecular weight of at least 1,000 Daltons or a weight average MW ranging from 2000 Daltons to 2,000,000 Daltons, 10,000 Daltons to 1,500,000 Daltons, 100,000 Daltons to 1,000,000 Daltons, and a solubility in tetrahydrofuran (THF) equal to or less than 1.0 micrograms / mL at 21°C at 1 atmosphere.
33. An S-linked quinone homopolymer obtained by the process according to claim 32.
34. A method for preparing an S-linked quinone copolymer, the method comprising Providing a redox-active monomer quinone monomer X1-M1-X2 and a redox-active monomer quinone monomer X1-M2-X2, wherein X1 and X2 represent leaving groups, Provide sulfide S p1 and S p2 The source, The redox active monomer quinone monomer X1-M1-X2 and the redox active monomer quinone monomer X1-M2-X2 are mixed with the sulfide S p1 and S p2 The source of is contacted under suitable conditions and for a sufficient period of time to provide an S-linked quinone copolymer represented by formula (II) -[M1-S p1 ] m1 -co-[M2-S p2 ]- m2 (II) in M1 and M2 are each a redox-active monomeric quinone moiety comprising a redox potential of 0.5 V to 3.5 V relative to the Li / Li+ electrode potential under standard conditions, p1 and p2 each independently refer to the number of sulfur atoms connected to the redox-active monomeric quinone moiety M1 and the monomeric quinone moiety M2, respectively, and p1 and p2 each independently range from 1 to 5, When p1 is 1, S p1 is a sulfide, or when p1 is 2 to 5, S p1 For polysulfide, When p2 is 1, S p2 is a sulfide, or when p2 is 2 to 5, S p2 For polysulfide, m1 and m2 each independently range from 5 to 5,000, optionally the ratio of m1 to m2 ranges from 1:50 to 1:1, 1:20 to 1:2, 1:6 to 1:3, or 1:5 to 1:4, wherein the S-linked quinone copolymer of formula (II) has a weight average molecular weight ranging from 1,000 Daltons to 2,000,000 Daltons, or a weight average MW ranging from 2000 Daltons to 2,000,000 Daltons, 10,000 Daltons to 1,500,000 Daltons, 100,000 Daltons to 1,000,000 Daltons, and a solubility in tetrahydrofuran (THF) equal to or less than 1.0 micrograms / mL at 21°C at 1 atmosphere.
35. An S-linked quinone copolymer obtained by the process according to claim 33.
36. An electrochemical cell comprising an anode, a cathode, and a non-aqueous electrolyte or an aqueous electrolyte, wherein the cathode electrode comprises the redox-active composition of claim 17.
37. A battery comprising one or more electrochemical cells according to claim 36.
Citation Information
Patent Citations
Crosslinked polymers and related compositions, electrochemical cells, batteries, methods and systems
US11739173B2
Cited By
Crosslinked polymers and related compositions, electrochemical cells, batteries, methods and systems
US12503539B2
